Method for producing adhesive sheet and adhesive sheet

By applying and permeating the additive solution on the cured adhesive layer, the problems of unstable changes in the properties of the adhesive sheet and small design freedom in the prior art are solved, and the optimized properties of the adhesive layer and efficient bonding reliability are achieved.

CN115397936BActive Publication Date: 2025-03-04NITTO DENKO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180024679.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-23
Filing Date
2021-03-24
Publication Date
2025-03-04
Estimated Expiration
2041-03-24

AI Technical Summary

Technical Problem

When the prior art mixes additives to the adhesive sheet, it is difficult to effectively control the physical properties changes of the adhesive sheet and the interference between the additives, resulting in unstable physical properties changes such as the adhesive force and elastic modulus of the adhesive layer, and the design freedom is small.

Method used

After curing the adhesive layer, the additive solution is applied and penetrated, thereby controlling the physical properties of the adhesive layer and the concentration gradient of the additive, thereby reducing interference between the additives and improving design freedom.

Benefits of technology

By this method, while maintaining the transparency of the adhesive layer, the physical properties of the adhesive layer can be optimized, the freedom to select additives and design of curing conditions can be improved, the physical properties of the adhesive layer can be reduced, and the adhesive reliability can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115397936B_ABST
    Figure CN115397936B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide a method for manufacturing an adhesive sheet and an adhesive sheet obtained by the manufacturing method, wherein even when an additive is added to the adhesive sheet, the change in the physical properties of the adhesive sheet and the interference between the additives are suppressed to a minimum, and the freedom of design of the selection of additives, curing conditions, etc. is increased to facilitate design. The manufacturing method of the adhesive sheet of the present invention is characterized in that it includes the following steps: forming an adhesive layer 10 formed of a transparent adhesive matrix material on a support S, curing the adhesive layer 10, preparing a solution 12 of an additive 11, applying the solution 12 on one surface of the cured adhesive layer 10a, allowing the additive 11 contained in the solution 12 to penetrate from the one surface of the adhesive layer 10a along the thickness direction, and drying the adhesive layer 10a.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an adhesive sheet having a transparent adhesive layer and an adhesive sheet obtainable by the production method. In particular, the present invention relates to a method for producing an adhesive sheet having a transparent adhesive layer that can be used to bond a transparent optical component to another optical component and an adhesive sheet obtainable by the production method. Background Art

[0002] Image display devices such as liquid crystal display devices and organic EL display devices are composed of optical component stacks stacked with transparent cover components such as polarizing films, phase difference films, cover glasses, and other various transparent optical components. In order to join these optical components, an adhesive sheet containing a transparent adhesive layer is used. That is, an adhesive sheet is arranged between two optical components to be joined, and the two optical components are joined by pressing them against each other to form an optical component stack. In addition, in the manufacturing process of optical products, an adhesive sheet having an adhesive layer on one side of a substrate film is usually used as a surface protection film for preventing the aforementioned optical components from being damaged or dirt from adhering.

[0003] The above-mentioned pressure-sensitive adhesive sheet may contain various additives such as a polymerization initiator, a crosslinking agent, a UV absorber, a rust preventive, and an antistatic agent depending on the required properties.

[0004] For example, in an image display device having an input device such as a touch panel, a transparent and conductive printed layer such as patterned ITO (indium tin oxide) is formed on the surface of an optical component. Furthermore, silver or copper pulling wiring is formed on the peripheral portion. In addition, a black shielding portion is usually printed in a frame shape on the edge of a transparent protective cover component. For an adhesive sheet that joins such an optical component having a printed layer and wiring, it is required to improve the fluidity of the adhesive layer and show height difference absorption such that no bubbles remain in the printed height difference.

[0005] On the other hand, plastic films used as optical components contain gases such as carbon dioxide, which may be generated under high temperature conditions during the manufacturing process. In this case, if the adhesive layer is soft, it is impossible to completely suppress the generation of gas, and there are problems such as the adhesive layer floating and bubbles being easily generated. Therefore, in order to suppress the generation of gas from the plastic film, the adhesive sheet is also required to increase the elastic modulus of the adhesive layer, strengthen the hardness, and improve the bonding reliability.

[0006] As an adhesive sheet that takes into account both the above-mentioned height difference absorbency and bonding reliability, an adhesive sheet containing a mixed adhesive (sometimes referred to as a "mixed adhesive sheet" in this specification) is widely used (for example, refer to Patent Document 1). A mixed adhesive is an adhesive composition that is mixed with two polymerization initiators and crosslinking agents (sometimes referred to as "initiators" in this specification) with different curing initiation conditions such as heat and light, and cured in stages. The mixed adhesive sheet has the following advantages: first, due to a kind of initiator (sometimes referred to as the "first initiator" in this specification), the fluidity is high, and a semi-cured state with excellent height difference absorbency is made so that it can fully follow the height difference. Thereafter, another initiator (sometimes referred to as the "second initiator" in this specification) is used to end the curing, thereby improving the bonding reliability.

[0007] In addition, in image display devices, in order to suppress the degradation of components in the image display device caused by incident ultraviolet rays, ultraviolet interception is sometimes sought. In particular, organic compounds are used as light-emitting elements in organic EL display devices, so the degradation caused by ultraviolet rays is faster than that of liquid crystal display devices. In addition, optical components such as polarizing films and protective films are gradually thinned, and the light resistance to ultraviolet rays is reduced, so an ultraviolet absorbing layer must be provided. For example, it is known to use an adhesive sheet having an ultraviolet absorbing layer containing an ultraviolet absorber (for example, see Patent Document 2).

[0008] In addition, in image display devices and input devices, as sensors become larger and narrower in frame, more and more copper wiring is used. Copper has excellent conductivity and is a useful material for wiring, but it is prone to oxidation / corrosion. In order to suppress oxidation / corrosion of copper wiring, it is known to mix a rust inhibitor into an adhesive sheet (for example, see Patent Document 3).

[0009] In addition, when peeling off the surface protection film from an optical component such as a polarizing film, if static electricity is generated, there is a concern that the circuit of the image display device may be damaged. In addition, static electricity may also attract dust or reduce workability. For example, in order to prevent static electricity from being generated by the surface protection film, it is known to mix an antistatic agent into the adhesive layer (for example, refer to Patent Document 4).

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: International Publication No. WO2016 / 170875

[0013] Patent Document 2: Japanese Patent Application Publication No. 2012-211305

[0014] Patent Document 3: International Publication No. WO2015 / 145767

[0015] Patent Document 4: Japanese Patent Application Publication No. 2016-128537 Summary of the invention

[0016] Problem that the invention aims to solve

[0017] When the above-mentioned various additives are compounded into the adhesive sheet, sometimes the various physical properties such as the adhesive force and elastic modulus of the adhesive sheet are affected. In particular, in recent years, due to the lightweight and thinning of the image display device, the thinning of the adhesive layer has also been carried out, and the requirement for increasing the concentration of the additives contained in the adhesive sheet to meet the required characteristics is increasing. In addition, the requirement for the adhesive sheet to be given multiple functions by compounding two or more additives is also gradually increased, but sometimes the additives interfere with each other and present a compromise relationship. Like this, the problem caused by compounding various additives in the adhesive sheet is more and more obvious.

[0018] In view of this background, when additives are compounded into an adhesive sheet, in addition to satisfying the required characteristics to be achieved by the additives, in order to reduce changes in physical properties such as the adhesive force and elastic modulus of the adhesive sheet and interference between the additives, it is necessary to design from scratch the compounding amount of various additives, the adhesive composition such as the monomer composition of the matrix polymer, the thickness of the adhesive sheet, the curing conditions, etc. Furthermore, in order to take into account both the required characteristics to be achieved by the additives and the physical properties of the adhesive sheet, there is also a problem that the degree of freedom in designing the additive selection, curing conditions, etc. is narrowed.

[0019] For example, in a mixed adhesive composition, since two initiators having different curing conditions are used in combination, it is necessary to set an initiator combination and strict curing conditions so that a curing reaction based on the second initiator does not occur when the first initiator is used. This leads to a problem that the design freedom of the selection of initiators, curing conditions, etc. becomes extremely narrow.

[0020] For example, when the first initiator is a thermal polymerization initiator and the second initiator is a photopolymerization initiator, the second initiator may be cured during the thermal curing of the first initiator, and the curing reaction needs to be strictly controlled. In addition, a thick adhesive layer also has the problem of time-consuming thermal curing and reduced production efficiency.

[0021] When the first initiator is a photopolymerization initiator and the second initiator is a thermal polymerization initiator, process management is required to prevent exposure to high temperatures in the process after photocuring. In addition, since heating is difficult after the adhesive sheet is attached, practicality is low.

[0022] When the first initiator and the second initiator are photopolymerization initiators, the light absorption wavelength bands of the two photopolymerization initiators need to be sufficiently offset. Furthermore, when the ultraviolet absorber is further compounded, the wavelength ranges also need to be differentiated, so the designability becomes extremely narrow.

[0023] When the first initiator and the second initiator are thermal polymerization initiators, thermal curing of the second initiator is inevitably performed during thermal curing of the first initiator, and therefore, it is difficult to perform a two-step curing reaction.

[0024] In addition, since a sufficient amount of ultraviolet absorber is added to impart ultraviolet interception properties to the adhesive composition, there is a problem of affecting the physical properties and curability of the adhesive. In particular, when a photocurable adhesive sheet containing an ultraviolet absorber is cured by irradiating ultraviolet rays, there is a problem that the ultraviolet rays are absorbed by the ultraviolet absorber, the curability deteriorates, and the productivity decreases.

[0025] Furthermore, the photocurable adhesive sheet mixed with an ultraviolet absorber also has the problem of differences in physical properties such as adhesion and viscoelasticity between the front and back sides of the adhesive sheet. This is because the ultraviolet rays are absorbed by the ultraviolet absorber during the process of passing through the inside of the adhesive layer, and the deeper from the ultraviolet irradiation side surface, the lower the ultraviolet irradiance, resulting in a difference in curing speed between the front and back sides.

[0026] In addition, in the above patent documents, additives are added to the adhesive composition and uniformly dissolved, but rust inhibitors, antistatic agents, etc. originally function only near the interface with the optical component to be bonded. However, there is a dilemma: in order to give the surface of the adhesive sheet sufficient rust prevention and antistatic functions, additives need to be added to the entire adhesive layer, but this will affect the physical properties of the adhesive sheet.

[0027] The present invention has been conceived based on the above situation, and its purpose is to provide a method for manufacturing an adhesive sheet, which can minimize the change in the physical properties of the adhesive sheet and the interference between the additives even when additives are mixed into the adhesive sheet, and improve the design freedom of additive selection, curing conditions, etc., so as to facilitate design.

[0028] Another object of the present invention is to provide an adhesive sheet in which, even when additives are added to the adhesive sheet, changes in the physical properties of the adhesive sheet and interference between the additives are minimized, and the degree of freedom in designing the additive selection, curing conditions, etc. is increased, thereby facilitating design.

[0029] Solutions for solving problems

[0030] The inventors of the present invention have conducted in-depth research to achieve the above-mentioned purpose, and found that after the adhesive layer of the adhesive sheet is cured, a solution of an additive is applied and infiltrated, so that the influence on the physical properties of the adhesive layer and the interference between the additives can be minimized, and the physical properties of the adhesive layer are excellent, and the adhesive sheet showing excellent required characteristics with the help of the additives can be obtained. In addition, it is found that the design freedom of additive selection, curing conditions, etc. is significantly improved. The present invention is completed based on these insights.

[0031] That is, the first aspect of the present invention provides a method for producing an adhesive sheet, comprising the following steps:

[0032] forming an adhesive layer formed of a transparent adhesive matrix material on a support,

[0033] The adhesive layer is cured.

[0034] Prepare the solution of additives,

[0035] The solution is applied to one surface of the cured adhesive layer, so that the additive contained in the solution permeates from the one surface of the adhesive layer in the thickness direction.

[0036] The adhesive layer is dried.

[0037] By curing the adhesive layer before adding the additive to the adhesive layer, the influence of the additive on the adhesive layer can be reduced, and thus the change in the physical properties of the adhesive layer caused by the additive can be minimized.

[0038] By applying a solution of an additive to the cured adhesive layer, the additive is allowed to penetrate into the adhesive layer. Thus, the adhesive layer can be endowed with the required characteristics achieved by the additive. In addition, by allowing the additive to penetrate in a solution state, the transparency of the adhesive layer can be maintained.

[0039] Thereafter, the adhesive layer is dried by heating or the like. Through this process, the adhesive layer is restored to a state close to that before coating. That is, the adhesive layer is temporarily cured so that the physical properties such as adhesive force and elastic modulus are restored to a state close to that before coating the above solution.

[0040] Since the adhesive layer is cured before the additive is added, once the composition, curing conditions, physical properties, etc. of the adhesive composition are determined, there is no need to redesign the composition achieved by mixing the additive, and it is also easy to change the thickness of the adhesive layer. In addition, by changing the coating conditions of the additive solution thereafter, it is possible to control the required characteristics given to the adhesive layer. In this way, since the physical property control of the adhesive layer and the control of the required characteristics achieved by the additive can be separated, there is no need to design the adhesive layer from scratch for changes in the thickness of the adhesive layer, the amount of additive added, etc., and the efficiency is good.

[0041] In the method for producing the adhesive sheet according to the first aspect of the present invention, the solution of the additive may be a solution obtained by dissolving the additive in a solvent, and may include a step of drying the adhesive layer to evaporate the solvent of the solution.

[0042] By applying a solution obtained by dissolving an additive in a solvent to the cured adhesive layer, the solvent penetrates into the adhesive layer to cause the adhesive layer to swell, and the additive dissolved in the solvent penetrates into the adhesive layer swollen by the solvent. Thus, the adhesive layer can be given the required characteristics achieved by the additive, and the transparency of the adhesive layer can be maintained by allowing the additive to penetrate in the form of a solution.

[0043] The solvent that has penetrated into the adhesive layer evaporates by heating or the like, and the adhesive layer returns to a state close to that before swelling. That is, the adhesive layer temporarily solidifies, and the physical properties such as adhesive force and elastic modulus return to a state close to that before the solution is applied.

[0044] Furthermore, by, for example, applying solutions of two or more additives to the pressure-sensitive adhesive layer and drying them separately, interference between the additives can be reduced, and a variety of required properties can be effectively imparted.

[0045] The method for producing the adhesive sheet of the first aspect of the present invention may further include a step of attaching a release sheet to the surface of the adhesive layer opposite to the support. Attaching a release sheet is preferred because the adhesive layer surface can be maintained.

[0046] In the method for producing an adhesive sheet according to the first aspect of the present invention, the additive may be at least one selected from the group consisting of a polymerization initiator, a crosslinking agent, a UV absorber, a rust preventive, and an antistatic agent. These additives are suitable examples for obtaining the predetermined effects of the present invention.

[0047] When the additive is at least one selected from a polymerization initiator and a crosslinking agent, the first aspect of the present invention is useful as a method for producing a hybrid adhesive sheet.

[0048] When the first aspect of the present invention is a method for producing a mixed adhesive sheet, it is preferred that:

[0049] The aforementioned adhesive matrix material contains a first polymerization initiator and a first cross-linking agent as a first initiator,

[0050] The curing is based on the reaction of the first polymerization initiator and the first crosslinking agent.

[0051] As the second initiator, the aforementioned additive is at least one selected from the group consisting of a second polymerization initiator and a second cross-linking agent.

[0052] In addition, the first polymerization initiator and the second polymerization initiator may be the same.

[0053] Since the curing reaction by the first initiator is completed before the second initiator is added, there is no need to set strict curing conditions for the combination with the first initiator that does not cause the curing reaction by the second initiator, which significantly improves the design freedom of the hybrid adhesive sheet.

[0054] That is, since the curing reactions of the first initiator and the second initiator are separate, the combination of the first initiator and the second initiator has a great degree of freedom in selection. For example, a combination in which the first initiator and the second initiator are both photopolymerization initiators, a combination in which the first initiator is a thermal polymerization initiator and the second initiator is a photopolymerization initiator, a combination in which the first initiator is a photopolymerization initiator and the second initiator is a thermal polymerization initiator, etc. can be freely selected. In addition, a combination in which the first initiator and the second initiator are both thermal polymerization initiators, which is difficult to achieve in conventional mixed adhesive sheets, can also be a combination in which the first initiator and the second initiator are both photopolymerization initiators. In addition, in the case of a combination in which the first initiator and the second initiator are both photopolymerization initiators, the light absorption wavelength bands of the two photopolymerization initiators may overlap or be similar.

[0055] Furthermore, a combination of the same polymerization initiator (either a thermal polymerization initiator or a photopolymerization initiator) may be used as the first initiator and the second initiator, which is impossible in conventional mixed adhesive sheets.

[0056] As described above, the degree of freedom in combining the first initiator and the second initiator is extremely high, and a combination of the same initiator is also suitable from the viewpoint of avoiding the use of a polymerization initiator that may cause coloration or degradation of the pressure-sensitive adhesive layer.

[0057] Furthermore, since the curing reactions of the first initiator and the second initiator are separate and do not interfere with each other, there is no need to set strict conditions for controlling the respective curing reactions. For example, the first initiator does not need to be set to a condition that does not cause a curing reaction based on the second initiator. Once the curing conditions that can impart excellent high-low absorption to the adhesive layer are determined, the adhesive reliability that should be imparted to the adhesive layer can be easily controlled by changing the coating conditions and curing conditions of the subsequent second initiator solution.

[0058] In the first aspect of the present invention, when the additive is a UV absorber, the adhesive layer can be cured by irradiating the adhesive layer with UV rays before adding the UV absorber, without being affected by the UV absorber. Therefore, changes in the physical properties of the adhesive layer such as reduced productivity and differences in physical properties between the front and back surfaces caused by deterioration of curability due to the UV absorber can be minimized.

[0059] In addition, since the adhesive layer is cured before the ultraviolet light absorber is added, once the composition, curing conditions, physical properties, etc. of the adhesive composition are determined, it is not necessary to redesign the composition achieved by mixing the ultraviolet light absorber, and it is also easy to change the thickness of the adhesive layer. In addition, by changing the coating conditions of the ultraviolet light absorber solution thereafter, it is possible to control the ultraviolet light absorption function imparted to the adhesive layer. In this way, since the physical property control of the adhesive layer and the control of the ultraviolet light absorption function can be separated, there is no need to design the adhesive layer from scratch for the change of the thickness of the adhesive layer and the ultraviolet light absorption function, and the efficiency is good.

[0060] In addition, for example, when a UV absorber is compounded into the mixed adhesive sheet, the UV absorber can be added after the curing based on the first initiator and the second initiator, so there is no need to distinguish the absorption wavelength bands of the photopolymerization initiator and the UV absorber used as the first initiator and the second initiator. Therefore, the degree of freedom of choice of the combination of the photopolymerization initiator and the UV absorber is also significantly improved.

[0061] In the first aspect of the present invention, when the additive is at least one selected from a polymerization initiator and a crosslinking agent, the additive preferably further comprises an ultraviolet absorber. By making the additive further comprise an ultraviolet absorber on the basis of comprising at least one selected from a polymerization initiator and a crosslinking agent, a mixed adhesive sheet comprising an ultraviolet absorber can be manufactured by a single coating, thereby improving manufacturing efficiency. In addition, if the mixed adhesive sheet comprising an ultraviolet absorber is irradiated with ultraviolet rays, the ultraviolet absorber that absorbs the ultraviolet rays generates heat and promotes the curing reaction, which can improve the bonding reliability, and is therefore more preferred.

[0062] In the first aspect of the present invention, when the additive is a rust preventive or an antistatic agent, a solution of the rust preventive or antistatic agent is applied to the surface of the cured adhesive layer and allowed to penetrate, thereby providing sufficient rust preventive or antistatic function to the vicinity of the surface of the adhesive layer. Since it is not necessary to evenly disperse the rust preventive or antistatic agent in the adhesive layer, changes in the physical properties of the adhesive layer such as the elastic modulus caused by the rust preventive or antistatic agent can be minimized, and the amount of the rust preventive or antistatic agent used can also be reduced.

[0063] In addition, owing to make adhesive layer solidify before adding rust preventer or antistatic agent, therefore, if once determine the composition, curing condition, physical property etc. of adhesive composition, then need not design again because of compounding rust preventer or antistatic agent and realize the composition, also easily change the thickness of adhesive layer.And, by changing the coating condition of the solution of rust preventer or antistatic agent thereafter, thereby can control the rust-proof function or the antistatic energy given to adhesive layer.Like this, owing to can be separated by the physical property control of adhesive layer and the control of rust-proof function or the antistatic energy realized by rust preventer or antistatic agent, therefore, for the change of the addition amount etc. of thickness of adhesive layer, rust preventer or antistatic agent, need not to carry out the design of adhesive layer from the beginning, good efficiency.

[0064] In addition, a second aspect of the present invention provides a method for producing an optical member stacked body, which is a method for producing an optical member stacked body including a substrate formed of an optical member and a pressure-sensitive adhesive layer, and includes the following steps:

[0065] The adhesive layer of the adhesive sheet obtained by the method for producing a hybrid adhesive sheet according to the first aspect of the present invention is bonded to the main surface of the substrate formed of the optical member.

[0066] The adhesive layer is cured by reaction of at least one selected from the group consisting of the second polymerization initiator and the second cross-linking agent.

[0067] In the method for producing an optical member stacked body according to the second aspect of the present invention, it is preferred that:

[0068] The main surface of the substrate formed of the optical member has a printed layer,

[0069] The adhesive layer is bonded to the printed layer so as to fill in a height difference between the main surface of the substrate formed of the optical member and the printed layer.

[0070] A second aspect of the present invention is a method for producing an optical member laminated body using an adhesive sheet (hybrid adhesive sheet) obtained by the method for producing a hybrid adhesive sheet according to the first aspect of the present invention.

[0071] The adhesive layer of the mixed adhesive sheet used in the second aspect of the present invention is cured by a first polymerization initiator and a first crosslinking agent (first initiator), and is in a semi-cured and highly fluid state before being cured by at least one (second initiator) selected from the group consisting of a second polymerization initiator and a second crosslinking agent. Therefore, even if the main surface of the substrate formed by the optical component has a printed layer, the adhesive layer can fully follow the height difference between the main surface of the substrate formed by the optical component and the printed layer, and join in a manner of filling it.

[0072] Next, by curing the adhesive layer by a reaction of at least one (second initiator) selected from the group consisting of the second polymerization initiator and the second crosslinking agent, the elastic modulus of the adhesive layer can be increased, and the adhesion reliability can be improved.

[0073] In addition, a third aspect of the present invention provides an adhesive sheet, characterized in that:

[0074] The invention comprises a support and a transparent adhesive layer on the support,

[0075] The adhesive layer is formed of a transparent adhesive matrix material and is a single layer having two opposing main surfaces.

[0076] The adhesive layer contains an additive dissolved therein.

[0077] When the above-mentioned single-layer adhesive layer is divided into two equal parts along the thickness direction,

[0078] The concentration of the additive in a region to which one of the two main surfaces, ie, the first main surface, belongs is different from the concentration of the additive in a region to which the other main surface, ie, the second main surface, belongs.

[0079] The adhesive sheet of the third aspect of the present invention is obtained by the method for manufacturing the adhesive sheet of the first aspect of the present invention. By applying a solution of an additive to one side of the adhesive layer and allowing it to penetrate, a concentration difference of the additive can be generated on the front and back sides of the adhesive layer. The adhesive capable of producing this structure can control the physical property changes caused by the additive to a minimum as described above.

[0080] It should be noted that in the method for manufacturing the adhesive sheet of the first aspect of the present invention, the concentration of the additive on the front and back sides of the adhesive layer may be the same or substantially the same, depending on the thickness of the adhesive layer, the penetration time of the additive, etc. Therefore, the situation in which the adhesive sheet having the same or substantially the same concentration of the additive on the front and back sides of the adhesive layer can be obtained by the method for manufacturing the adhesive sheet of the first aspect of the present invention is also included in the present invention.

[0081] In the adhesive sheet according to the third aspect of the present invention, it is preferred that the adhesive layer is a cured adhesive layer. This configuration is preferred in that changes in physical properties due to additives can be minimized.

[0082] In the adhesive sheet of the third aspect of the present invention, it is preferred that: the second main surface faces the support, and the concentration of the additive in the region to which the first main surface belongs is higher than the concentration of the additive in the region to which the second main surface belongs. This configuration can be obtained by coating a solution of the additive on the first main surface.

[0083] In the third aspect of the adhesive sheet of the present invention, it is preferred that the single adhesive layer has a concentration gradient of the additive along the thickness direction. This configuration can be obtained by applying a solution of the additive to one main surface of the adhesive layer and allowing it to penetrate.

[0084] In the adhesive sheet of the third aspect of the present invention, it is preferred that the support body is formed of a release sheet. In this case, the support body formed of a release sheet is preferably arranged on both sides of the adhesive layer. It is preferred that the support body is a release sheet so that it can be bonded to a transparent optical member after peeling.

[0085] In the adhesive sheet according to the third aspect of the present invention, the additive is preferably at least one selected from the group consisting of a polymerization initiator, a crosslinking agent, a UV absorber, a rust preventive, and an antistatic agent. These additives are suitable examples for obtaining the predetermined effects of the present invention.

[0086] When the additive is at least one selected from the group consisting of a polymerization initiator and a crosslinking agent, the third aspect of the present invention is useful as a hybrid adhesive sheet.

[0087] In the third aspect of the present invention, when the additive is at least one selected from a polymerization initiator and a crosslinking agent, the additive preferably further comprises an ultraviolet absorber. When the additive further comprises an ultraviolet absorber on the basis of comprising at least one selected from a polymerization initiator and a crosslinking agent, the adhesive sheet of the third aspect of the present invention can form a mixed adhesive sheet comprising an ultraviolet absorber. If the mixed adhesive sheet comprising an ultraviolet absorber is irradiated with ultraviolet rays, the ultraviolet absorber that absorbs ultraviolet rays generates heat to promote the curing reaction, which can improve the bonding reliability, and is preferred from this point of view.

[0088] When the third aspect of the present invention is a mixed adhesive sheet, it is preferred that:

[0089] The aforementioned adhesive matrix material comprises a first polymerization initiator and a first cross-linking agent as a first initiator,

[0090] The curing is based on the reaction of the first polymerization initiator and the first crosslinking agent.

[0091] As the second initiator, the aforementioned additive is at least one selected from the group consisting of a second polymerization initiator and a second cross-linking agent.

[0092] In addition, the first polymerization initiator and the second polymerization initiator may be the same.

[0093] When the third aspect of the present invention is a mixed adhesive sheet, the same effects as when the first aspect of the present invention is a method for producing a mixed adhesive sheet can be achieved.

[0094] In addition, by making the concentration of the second initiator in the area to which the first main surface belongs different from the concentration of the second initiator in the area to which the second main surface belongs, the crosslinking density of the first main surface and the second main surface can be controlled, and the physical properties such as the elastic modulus on the front and back sides of the adhesive layer can be different. This structure is suitable in, for example, a bendable flexible display. When a flexible display is bent, a tensile stress is usually applied to the outside and a compressive stress is applied to the inside, and the stress on the outside is stronger than the stress on the inside. Therefore, by configuring the side of the adhesive layer with a high concentration of the second initiator to the outside when the flexible display is bent, the durability against bending can be improved.

[0095] In the adhesive sheet of the third aspect of the present invention, when the additive is a UV absorber, the same effect as the case where the additive is a UV absorber in the method for manufacturing the adhesive sheet of the first aspect of the present invention can be exerted. That is, the adhesive sheet of the third aspect of the present invention in which the additive is a UV absorber can minimize the decrease in productivity caused by the deterioration of curing property caused by the UV absorber, the difference in physical properties between the front and back surfaces, and other physical property changes.

[0096] In the adhesive sheet of the third aspect of the present invention, when the additive is a rust inhibitor or an antistatic agent, the same effect as the situation where the additive in the manufacture method of the adhesive sheet of the first aspect of the present invention is a rust inhibitor or an antistatic agent can be achieved. That is, the adhesive sheet of the third aspect of the present invention in which the additive is a rust inhibitor or an antistatic agent can be distributed on a principal surface (the first principal surface or the second principal surface) with a higher concentration by making the rust inhibitor or the antistatic agent be distributed on the principal surface, thereby excellent rust-proof function or antistatic function can be given to the principal surface. Due to the need not to make the rust inhibitor or the antistatic agent be uniformly dispersed in the adhesive layer, thereby the physical property change of the adhesive layer caused by the rust inhibitor or the antistatic agent can be controlled to be minimum, and the consumption of the rust inhibitor or the antistatic agent can also be reduced.

[0097] In the adhesive sheet of the third aspect of the present invention, the thickness of the adhesive layer is preferably 5 μm to 500 μm. If the thickness of the adhesive layer is within this range, it is suitable on the basis of forming a concentration gradient of the additive along the thickness direction of the adhesive layer. The thickness of the adhesive layer is more preferably 5 μm to 400 μm, and further preferably 5 μm to 350 μm.

[0098] In addition, a fourth aspect of the present invention provides an optical member stack including:

[0099] a substrate formed of optical components; and

[0100] Adhesive layer,

[0101] The adhesive layer is laminated on the main surface of the substrate formed of the optical member.

[0102] The aforementioned adhesive layer is a cured product of the adhesive layer of the hybrid adhesive sheet according to the third aspect of the present invention.

[0103] In the fourth aspect of the present invention, it is preferred that:

[0104] The main surface of the substrate formed of the optical member has a printed layer,

[0105] The pressure-sensitive adhesive layer is laminated so as to fill a height difference between the main surface of the substrate formed of the optical member and the printed layer.

[0106] In addition, in the fourth aspect of the present invention, it is preferred that:

[0107] The cured product is a cured product obtained by a reaction of at least one selected from the group consisting of the second polymerization initiator and the second cross-linking agent.

[0108] A fourth aspect of the present invention is an optical member laminated body obtained by using the mixed adhesive sheet according to the third aspect of the present invention.

[0109] The optical member stacked body according to the fourth aspect of the present invention can be produced by the method according to the second aspect of the present invention, and can exhibit the same effects.

[0110] Effects of the Invention

[0111] According to the method for producing an adhesive sheet and the adhesive sheet of the present invention, even when additives are blended into the adhesive sheet, changes in the physical properties of the adhesive layer and interference between the additives are unlikely to occur.

[0112] Furthermore, it is not necessary to design the adhesive layer from scratch to change the thickness of the adhesive layer or the amount of additives added, which is highly efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0113] Figure 1 The present invention shows processes for implementing an embodiment of a method for manufacturing an adhesive sheet of the present invention, wherein (a) is a schematic diagram showing an adhesive layer forming process, (b) is a schematic diagram showing an adhesive layer curing process, (c) is a schematic diagram showing a solution coating process, (d) is a schematic diagram showing a solution penetration process, and (e) is a schematic diagram showing a drying process.

[0114] Figure 2 (a) is a cross-sectional view showing one embodiment of the adhesive sheet of the present invention, Figure 2 (b) is a cross-sectional view showing another embodiment of the adhesive sheet of the present invention.

[0115] Figure 3 This is a cross-sectional view of an optical member laminated body showing an example of the simplest embodiment using the adhesive sheet of the present invention.

[0116] Figure 4 This is a schematic diagram showing the steps for carrying out one embodiment of the method for producing an optical member laminated body obtained by using the hybrid adhesive sheet of the present invention.

[0117] Figure 5 It is a graph showing the TOF-SIMS analysis results of the adhesive sheets of Example 9 and Comparative Example 9. Figure 5 (a) is the result of Example 9, Figure 5 (b) is the result of Comparative Example 9. Figure 5 In the graph, the scale of the left vertical axis represents the intensity of butyl acrylate (BA) and N-vinyl pyrrolidone (NVP), and the scale of the right vertical axis represents the intensity of the ultraviolet absorber (Tinosorb S). DETAILED DESCRIPTION

[0118] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited thereto and is merely an example.

[0119] Figure 1 (a) to (e) are views schematically showing steps of one embodiment of a method for producing a pressure-sensitive adhesive sheet according to the first aspect of the present invention.

[0120] First, if Figure 1 As shown in (a) of FIG. 1 , an adhesive layer 10 made of a transparent adhesive matrix material is formed on a support S1 (adhesive layer forming step).

[0121] The support is not particularly limited, but preferably a plastic film. As the raw materials of the plastic film, polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, cellulose triacetate (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymer, cyclic olefin polymers such as "ARTON" (cyclic olefin polymer, manufactured by JSR Corporation), and "ZEONOR" (cyclic olefin polymer, manufactured by ZEON Corporation, Japan) can be cited. It should be noted that only one of these plastic materials can be used, or two or more can be used.

[0122] The support may be a release sheet. The release sheet is not particularly limited, and examples thereof include plastic films surface-treated with a release agent such as a silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide release agent.

[0123] As long as the aforementioned adhesive matrix material is a transparent material with adhesiveness that can be used in optical applications, there is no particular limitation. It can be appropriately selected from, for example, acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives and polyether adhesives for use. From the viewpoints of transparency, processability and durability, it is preferred to use acrylic adhesives. The aforementioned adhesive matrix material can use any one of the aforementioned adhesives alone, or two or more can also be used in combination. The acrylic polymer used as the matrix polymer of the acrylic adhesive has no particular meaning, and is preferably a homopolymer or copolymer of a monomer with (meth) alkyl acrylate as the main component. Here, the expression "(meth) acrylic acid" is used to refer to any one or both of "acrylic acid" and "methacrylic acid", and other situations are also the same. In the present invention, the term acrylic polymer is used with the meaning of other monomers that can copolymerize with it in addition to the above-mentioned (meth) alkyl acrylate.

[0124] When the aforementioned adhesive matrix material contains an acrylic polymer as an acrylic adhesive, the acrylic polymer preferably contains monomer units derived from an alkyl acrylate having a linear or branched alkyl group and / or an alkyl methacrylate having a linear or branched alkyl group as main monomer units with the largest weight proportion.

[0125] Examples of the (meth)acrylic acid alkyl ester having a linear or branched alkyl group used in the monomer unit forming the acrylic polymer, that is, the (meth)acrylic acid alkyl ester having a linear or branched alkyl group contained in the monomer component forming the acrylic polymer, include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, and tert-butyl (meth)acrylate. Alkyl (meth)acrylates having a linear or branched alkyl group with 1 to 20 carbon atoms, such as 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. As the alkyl (meth)acrylate used for the acrylic polymer, one alkyl (meth)acrylate may be used, or two or more alkyl (meth)acrylates may be used. In the present embodiment, as the alkyl (meth)acrylate used for the acrylic polymer, at least one selected from the group consisting of n-butyl acrylate, 2-ethylhexyl acrylate, and isostearyl acrylate is preferably used.

[0126] The ratio of the monomer units derived from the (meth)acrylic acid alkyl ester having a linear or branched alkyl group in the acrylic polymer is preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, and more preferably 90% by weight or more. In other words, the ratio of the (meth)acrylic acid alkyl ester in the monomer component composition of the raw material for forming the acrylic polymer is preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, and more preferably 90% by weight or more.

[0127] The acrylic polymer contained in the aforementioned adhesive matrix material may include monomer units derived from alicyclic monomers. As alicyclic monomers used to form monomer units of acrylic polymers, that is, alicyclic monomers contained in monomer components used to form the acrylic polymers, for example, cycloalkyl (meth)acrylates, (meth)acrylates having a bicyclic hydrocarbon ring, and (meth)acrylates having a hydrocarbon ring of three or more rings can be cited. As cycloalkyl (meth)acrylates, for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate can be cited. As (meth)acrylates having a bicyclic hydrocarbon ring, for example, bornyl (meth)acrylate and isobornyl (meth)acrylate can be cited. As (meth)acrylates having three or more hydrocarbon rings, for example, dicyclopentanyl (meth)acrylate, dicyclopentyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate can be cited. As alicyclic monomers for acrylic polymers, one alicyclic monomer can be used, or two or more alicyclic monomers can be used. In the present embodiment, as alicyclic monomers for acrylic polymers, at least one selected from the group consisting of cyclohexyl acrylate, cyclohexyl methacrylate, isobornyl acrylate, and isobornyl methacrylate is preferably used.

[0128] From the viewpoint of achieving appropriate flexibility of the adhesive matrix material formed by including the acrylic polymer, the ratio of the monomer units derived from the alicyclic monomer in the acrylic polymer is preferably 5 to 60 wt %, more preferably 10 to 50 wt %, and even more preferably 12 to 40 wt %.

[0129] The acrylic polymer contained in the aforementioned adhesive matrix material can include monomer units derived from hydroxyl-containing monomers. Hydroxyl-containing monomers are monomers having at least one hydroxyl group in the monomer unit. When the acrylic polymer in the adhesive matrix material includes hydroxyl-containing monomer units, it is easy to make the adhesive matrix material obtain adhesion and appropriate cohesion. In addition, hydroxyl groups can also become reaction sites for reacting with crosslinking agents described later.

[0130] As the hydroxyl-containing monomer used to form the monomer unit of the acrylic polymer, that is, the hydroxyl-containing monomer contained in the monomer component used to form the acrylic polymer, for example, hydroxyl-containing (meth)acrylates, vinyl alcohol and allyl alcohol can be listed. As the hydroxyl-containing (meth)acrylates, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate can be listed. As the hydroxyl-containing monomer used for the acrylic polymer, one hydroxyl-containing monomer can be used, or two or more hydroxyl-containing monomers can be used. In this embodiment, as the hydroxyl-containing monomer used for the acrylic polymer, at least one selected from the group consisting of 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate and 4-hydroxybutyl methacrylate is preferably used.

[0131] The proportion of monomer units derived from hydroxyl-containing monomers in the acrylic polymer is preferably 1% by weight or more, more preferably 2% by weight or more, more preferably 3% by weight or more, more preferably 7% by weight or more, more preferably 10% by weight or more, and more preferably 15% by weight or more. The proportion of monomer units derived from hydroxyl-containing monomers in the acrylic polymer is preferably 35% by weight or less, more preferably 30% by weight or less. These structures related to the proportion of hydroxyl-containing monomers are suitable for achieving adhesion and appropriate cohesive force in the adhesive matrix material formed by containing the acrylic polymer.

[0132] The acrylic polymer contained in the aforementioned adhesive matrix material may contain monomer units derived from nitrogen-containing monomers. Nitrogen-containing monomers are monomers having at least one nitrogen atom in the monomer unit. When the acrylic polymer in the adhesive matrix material contains nitrogen-containing monomer units, it is easy to make the adhesive matrix material obtain hardness and good bonding reliability.

[0133] Examples of nitrogen-containing monomers for forming the monomer units of the acrylic polymer, i.e., nitrogen-containing monomers contained in the monomer components for forming the acrylic polymer, include N-vinyl cyclic amides and (meth)acrylamides. Examples of N-vinyl cyclic amides that are nitrogen-containing monomers include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione. Examples of (meth)acrylamides that are nitrogen-containing monomers include (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, N-octyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, and N,N-diisopropyl (meth)acrylamide. As nitrogen-containing monomers for acrylic polymers, one nitrogen-containing monomer may be used, or two or more nitrogen-containing monomers may be used. In the present embodiment, N-vinyl-2-pyrrolidone is preferably used as a nitrogen-containing monomer for acrylic polymers.

[0134] The ratio of the monomer units derived from the nitrogen atom-containing monomer in the acrylic polymer is preferably 1% by weight or more, more preferably 3% by weight or more, and more preferably 5% by weight or more, in terms of achieving appropriate hardness, adhesion, and transparency in the adhesive matrix material formed by including the acrylic polymer. In addition, the ratio of the monomer units derived from the nitrogen atom-containing monomer in the acrylic polymer is preferably 30% by weight or less, and more preferably 25% by weight or less, in terms of achieving sufficient transparency and preventing the adhesive from becoming too hard and achieving good adhesion reliability in the adhesive matrix material formed by including the acrylic polymer.

[0135] The acrylic polymer contained in the aforementioned adhesive matrix material can include monomeric units derived from carboxyl-containing monomers. Carboxyl-containing monomers are monomers having at least one carboxyl group in the monomeric unit. When the acrylic polymer in the adhesive matrix material includes carboxyl-containing monomeric units, the adhesive matrix material is sometimes provided with good bonding reliability. In addition, carboxyl group can also become a reaction site with a crosslinking agent described later.

[0136] As the carboxyl-containing monomers used to form the monomer units of the acrylic acid polymer, that is, the carboxyl-containing monomers contained in the monomer components used to form the acrylic acid polymer, for example (meth) acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid and isocrotonic acid can be listed. As the carboxyl-containing monomers used for acrylic acid polymers, one carboxyl-containing monomer can be used, or two or more carboxyl-containing monomers can be used. In the present embodiment, as the carboxyl-containing monomers used for acrylic acid polymers, acrylic acid is preferably used.

[0137] The ratio of the monomer units derived from the carboxyl group-containing monomer in the acrylic polymer is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, in the adhesive matrix material formed by including the acrylic polymer, from the viewpoint of obtaining the contribution of the interaction between the polar group and the carboxyl group when the polar group exists on the adherend surface and ensuring good bonding reliability. In addition, the ratio of the monomer units derived from the carboxyl group in the acrylic polymer is preferably 20% by weight or less, more preferably 15% by weight or less, from the viewpoint of preventing the adhesive matrix material formed by including the acrylic polymer from becoming too hard and achieving good bonding reliability.

[0138] The acrylic polymer contained in the aforementioned adhesive matrix material may have a cross-linked structure derived from a cross-linking agent. By making the aforementioned adhesive matrix material have a cross-linked structure, the viscosity increases, the shape stability is improved, and it is easy to form an adhesive layer on the support S1. As the cross-linking agent, multifunctional (meth) acrylates and thermosetting cross-linking agents belonging to copolymerizable cross-linking agents can be listed. The aforementioned acrylic polymer may have a cross-linked structure derived only from multifunctional (meth) acrylates, may have a cross-linked structure derived only from a thermosetting cross-linking agent, and may also have a cross-linked structure derived from both multifunctional (meth) acrylates and thermosetting cross-linking agents.

[0139] In addition, this crosslinking agent is a crosslinking agent (first crosslinking agent) which constitutes a first initiator when the adhesive sheet of the present invention is a mixed adhesive sheet.

[0140] As the multifunctional (meth)acrylate, for example, 1,6-hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, and vinyl (meth)acrylate can be cited. As the multifunctional (meth)acrylate for acrylic polymer, one multifunctional (meth)acrylate can be used, or two or more multifunctional (meth)acrylates can be used. In the present embodiment, as the multifunctional (meth)acrylate for acrylic polymer, at least one selected from the group consisting of 1,6-hexanediol diacrylate, dipentaerythritol hexaacrylate, and trimethylolpropane triacrylate is preferably used.

[0141] The proportion of monomer units derived from multifunctional (meth)acrylates in the acrylic polymer is preferably 0.01% by weight or more, more preferably 0.03% by weight or more, more preferably 0.05% by weight or more, and more preferably 0.1% by weight or more. The proportion of monomer units derived from multifunctional (meth)acrylates in the acrylic polymer is preferably 1% by weight or less, more preferably 0.5% by weight or less. These structures related to the proportion of multifunctional (meth)acrylates are suitable for achieving appropriate hardness, adhesion, and shape stability of the adhesive matrix material formed by containing the acrylic polymer.

[0142] As the thermosetting crosslinking agent, for example, isocyanate crosslinking agent, epoxy crosslinking agent, metal chelate crosslinking agent, melamine crosslinking agent, peroxide crosslinking agent, urea crosslinking agent, metal alkoxide crosslinking agent, metal salt crosslinking agent, carbodiimide crosslinking agent, oxazoline crosslinking agent, aziridine crosslinking agent and amine crosslinking agent can be listed. The adhesive matrix material can contain one of the thermosetting crosslinking agents, or can contain two or more of the thermosetting crosslinking agents. Preferably, at least one selected from the group consisting of isocyanate crosslinking agent and epoxy crosslinking agent is used.

[0143] As isocyanate-based crosslinking agents, for example, lower aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates can be cited. As lower aliphatic polyisocyanates, for example, 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexylene diisocyanate can be cited. As alicyclic polyisocyanates, for example, cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate can be cited. As aromatic polyisocyanates, for example, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate can be cited. In addition, examples of isocyanate crosslinking agents include commercially available products such as trimethylolpropane / toluene diisocyanate adduct (trade name "CORONATE L", manufactured by Nippon Polyurethane Industries, Ltd.), trimethylolpropane / hexamethylene diisocyanate adduct (trade name "CORONATE HL", manufactured by Nippon Polyurethane Industries, Ltd.), and trimethylolpropane / xylylene diisocyanate adduct (trade name "TAKENATE D-110N", manufactured by Mitsui Chemicals, Inc.).

[0144] Examples of epoxy crosslinking agents (polyfunctional epoxy compounds) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether. Diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, triglycidyl-tris (2-hydroxyethyl) isocyanurate, resorcinol diglycidyl ether and bisphenol-S-diglycidyl ether. In addition, as epoxy crosslinking agents, epoxy resins having two or more epoxy groups can also be listed. And, as epoxy crosslinking agents, commercial products such as trade name "TETRAD C" (Mitsubishi Gas Chemical Co., Ltd.) can also be listed.

[0145] When the above-mentioned adhesive matrix material contains the above-mentioned thermosetting crosslinking agent for crosslinking acrylic polymers, the content of the thermosetting crosslinking agent in the adhesive matrix material is preferably 0.001 parts by weight or more, more preferably 0.01 parts by weight or more, relative to 100 parts by weight of the acrylic polymer in the adhesive matrix material, from the viewpoint of improving the shape stability of the adhesive matrix material, facilitating the formation of the adhesive layer on the support S1, and achieving sufficient bonding reliability for the adherend. In addition, from the viewpoint of making the adhesive matrix material exhibit appropriate flexibility and achieving good adhesive strength, the content of the thermosetting crosslinking agent in the adhesive matrix material is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, relative to 100 parts by weight of the acrylic polymer in the adhesive matrix material.

[0146] When the adhesive matrix material contains the above-mentioned acrylic polymer as the adhesive, the content of the acrylic polymer in the adhesive matrix material is, for example, 85 to 100% by weight.

[0147] The adhesive matrix material may contain a polymerization initiator in addition to the monomer and crosslinking agent for forming the acrylic polymer. Examples of the polymerization initiator include photopolymerization initiators and thermal polymerization initiators. The adhesive matrix material may contain one polymerization initiator or two or more polymerization initiators.

[0148] In addition, this polymerization initiator is a polymerization initiator (first polymerization initiator) which constitutes a first initiator when the adhesive sheet of the present invention is a mixed adhesive sheet.

[0149] Examples of the photopolymerization initiator include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators. Examples of the benzoin ether-based photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethane-1-one. As acetophenone-based photopolymerization initiators, for example, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone and 4-(tert-butyl)dichloroacetophenone can be listed. As α-ketol-based photopolymerization initiators, for example, 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one can be listed. As aromatic sulfonyl chloride-based photopolymerization initiators, for example, 2-naphthalenesulfonyl chloride can be listed. As photoactive oxime-based photopolymerization initiators, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)oxime can be listed. As benzoin-based photopolymerization initiators, for example, benzoin can be listed. As benzil-based photopolymerization initiators, for example, benzil can be listed. Examples of benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and polyvinylbenzophenone. Examples of ketal-based photopolymerization initiators include benzyldimethylketal. Examples of thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.

[0150] The amount of the photopolymerization initiator used is not particularly limited, and is, for example, preferably 0.001 to 1 part by weight, more preferably 0.01 to 0.50 part by weight, based on 100 parts by weight of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer).

[0151] Examples of the thermal polymerization initiator include azo-based polymerization initiators, peroxide-based polymerization initiators, and redox-based polymerization initiators. Examples of the azo-based polymerization initiator include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile (AMBN), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis-4-cyanovaleric acid, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(2,4,4-trimethylpentane). Examples of the peroxide polymerization initiator include benzoyl peroxide, tert-butyl peroxide, di-tert-butyl peroxide, tert-butyl peroxybenzoate, diisopropylbenzene peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-bis(tert-butylperoxy)cyclododecane.

[0152] The amount of the thermal polymerization initiator used is not particularly limited, and is, for example, preferably 0.05 to 0.5 parts by weight, more preferably 0.1 to 0.3 parts by weight, based on 100 parts by weight of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer).

[0153] The aforementioned adhesive matrix material may further contain additives such as crosslinking accelerators, silane coupling agents, tackifying resins, antioxidants, fillers, colorants such as pigments and dyes, antioxidants, chain transfer agents, plasticizers, softeners, surfactants, etc. as needed. As tackifying resins, for example, rosin derivatives, polyterpene resins, petroleum resins, and oil-soluble phenols may be cited.

[0154] It should be noted that when the additive described later is a UV absorber, the aforementioned adhesive matrix material preferably does not contain or substantially does not contain a UV absorber. This configuration is preferred from the viewpoint that the deterioration of curability, the difference in physical properties of the front and back sides, etc. can be controlled to a minimum when the adhesive sheet of the present invention is supplied to the adhesive layer curing process described later. When the ratio of the UV absorber in the total amount (100% by mass) of the adhesive matrix material is less than 0.05% by weight (preferably less than 0.01% by mass), it can be said that the aforementioned adhesive matrix material substantially does not contain a UV absorber.

[0155] In addition, when the additive described later is a rust inhibitor, the aforementioned adhesive matrix material preferably does not contain or substantially does not contain a rust inhibitor. This configuration is preferred from the viewpoint of being able to minimize the effect of the rust inhibitor on the adhesive layer of the adhesive sheet of the present invention. When the proportion of the rust inhibitor in the total amount (100% by mass) of the adhesive matrix material is 0.05% by weight or less (preferably 0.01% by mass or less), it can be said that the aforementioned adhesive matrix material substantially does not contain a rust inhibitor.

[0156] In addition, when the additive described later is an antistatic agent, the aforementioned adhesive matrix material preferably does not contain or substantially does not contain an antistatic agent. This configuration is preferred from the viewpoint of being able to control the influence of the antistatic agent on the adhesive layer of the adhesive sheet of the present invention to a minimum. When the ratio of the antistatic agent in the total amount (100% by mass) of the adhesive matrix material is less than 0.05% by weight (preferably less than 0.01% by mass), it can be said that the aforementioned adhesive matrix material substantially does not contain an antistatic agent.

[0157] The method for forming the adhesive layer is not particularly limited, and examples thereof include: applying (coating) the adhesive matrix material on a support, and drying and curing the resulting adhesive composition layer; applying (coating) the adhesive matrix material on a support, and curing the resulting adhesive composition layer by irradiating active energy rays. If necessary, further heating and drying may be performed.

[0158] The aforementioned adhesive matrix material can be applied (coated) using a known coating method, for example, coating machines such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a knife coater, a spray coater, a comma coater, and a direct coater.

[0159] The drying and curing temperature is preferably 40 to 200° C., more preferably 50 to 180° C., and further preferably 60 to 170° C. The drying and curing time can be appropriately set to a suitable time, for example, 5 seconds to 20 minutes, preferably 5 seconds to 10 minutes, and more preferably 10 seconds to 5 minutes.

[0160] As the above-mentioned active energy rays, for example, ionizing radiation such as α rays, β rays, γ rays, neutron rays, electron rays, ultraviolet rays, etc. can be listed, and ultraviolet rays are particularly preferred. In addition, the irradiation energy, irradiation time, irradiation method, etc. of the active energy rays are not particularly limited, as long as they are appropriately set in a manner to achieve a desired viscosity and viscoelasticity according to the thickness of the adhesive layer 10, etc.

[0161] In order to isolate oxygen that inhibits photocuring when the adhesive layer is photocured by irradiation with the above-mentioned active energy rays and / or ultraviolet rays described later, it is preferred that another support (including a release sheet) is further laminated on the main surface of the adhesive layer formed as above that does not face the support.

[0162] Next, the adhesive layer 10 is cured (adhesive layer curing step). Figure 1In (b), 10a is an adhesive layer obtained by curing the adhesive layer 10. The method for curing the adhesive layer 10 is not particularly limited, and examples thereof include heating the adhesive layer 10 and curing the adhesive layer 10 by irradiating the adhesive layer 10 with active energy rays. If necessary, further heating and drying may be performed. Examples of active energy rays include ionizing radiation such as α rays, β rays, γ rays, neutron rays, and electron rays; ultraviolet rays, etc., and ultraviolet rays are particularly preferred.

[0163] The conditions for curing the adhesive layer 10 can be appropriately selected according to the embodiment so that the adhesive layer 10 a has desired physical properties.

[0164] For example, when the adhesive matrix material in the adhesive sheet of the present invention is a mixed adhesive sheet containing the aforementioned polymerization initiator and crosslinking agent, the heating temperature, time or irradiation amount of active energy rays can be appropriately set so that the adhesive layer 10a exhibits high fluidity and excellent high-low difference absorption.

[0165] On the other hand, when the additive described later is a UV absorber, a rust preventive or an antistatic agent, the heating temperature, time or irradiation dose of active energy rays may be appropriately set so that the adhesive layer 10a exhibits a high elastic modulus and excellent bonding reliability.

[0166] Figure 1 (b) is an embodiment in which the adhesive layer 10 is cured by irradiating the adhesive layer 10 with ultraviolet rays U. The adhesive layer 10 may be irradiated directly with ultraviolet rays, but is preferably irradiated through a support in order to block oxygen that inhibits curing by ultraviolet irradiation. Figure 1 (b) is an embodiment of irradiating the adhesive layer 10 with ultraviolet rays through the support S2. When irradiating with ultraviolet rays through the support, another support S2 (including a release sheet) is attached to the main surface of the adhesive layer 10 on the opposite side of the main surface facing the support S1, and ultraviolet rays are irradiated through the support. The illumination and time of ultraviolet irradiation are appropriately set according to the composition of the adhesive matrix material, the thickness of the adhesive layer, etc. Ultraviolet irradiation can use a high-pressure mercury lamp, a low-pressure mercury lamp, a metal halide lamp, etc.

[0167] Then, if Figure 1As shown in (c), after the support body S2 is peeled off and removed, the solution 12 of the additive 11 is applied to one surface of the adhesive layer 10a (solution coating process). The solution of the additive is not particularly limited as long as it can be applied to the adhesive layer in a liquid state and penetrate. For example, when the additive is in a liquid state, the additive itself can be directly applied in the form of a solution. In addition, it can also be a solution obtained by dissolving the additive in a solvent. Alternatively, when the additive is a combination of two or more (for example, a second polymerization initiator as a second initiator and a second cross-linking agent), it can also be a solution obtained by mixing them. Figure 1 (c) is an embodiment in which a solution 12 obtained by dissolving the additive 11 in the solvent 13 is applied to one surface of the pressure-sensitive adhesive layer 10 a .

[0168] Regarding the surface of the adhesive layer 10a, the additive 11 in the solution 12 permeates into the adhesive layer 10a along the thickness direction (solution permeation step). Figure 1 (d). When the solution 12 is a solution obtained by dissolving the additive 11 in the solvent 13, the solvent 13 penetrates into the surface of the adhesive layer 10a to cause swelling, and the additive 11 penetrates into the adhesive layer 10a while being dissolved in the solvent. The additive 11 is in a state of being "dissolved" in the adhesive layer 10a.

[0169] In addition, during the process of the additive 11 penetrating into the adhesive layer 10a, a concentration gradient can be formed along the thickness direction. Therefore, the concentration of the additive 11 on the side coated with the solution 12 can be higher than that on the opposite side. Figure 1 (d).

[0170] Thereafter, the adhesive layer 10a is dried to obtain Figure 1 The adhesive sheet 1 shown in (e) (drying process). When the solution 12 is a solution obtained by dissolving the additive 11 in the solvent 13, the solvent 13 that has penetrated is evaporated by the drying process. By drying the adhesive layer 10a, the adhesive layer 10a is restored to a state close to that before coating. Therefore, the change in the physical properties of the adhesive layer 10a caused by the additive 11 can be controlled to a minimum. At the moment when the adhesive layer 10a is dried, the additive 11 stops penetrating into the adhesive layer 10a, and the concentration gradient of the aforementioned additive is fixed.

[0171] As the aforementioned additives, any additive added in the field of adhesives can be used without particular limitation, and examples thereof include polymerization initiators, crosslinking agents, ultraviolet absorbers, rust inhibitors, antistatic agents, crosslinking accelerators, silane coupling agents, tackifying resins, antioxidants, colorants such as dyes, antioxidants, chain transfer agents, plasticizers, softeners, surfactants, etc. From the viewpoint of easily exerting the desired effect of the present invention, polymerization initiators, crosslinking agents, ultraviolet absorbers, rust inhibitors, and antistatic agents are preferred.

[0172] It should be noted that the aforementioned additive is not preferably an acid. That is, the aforementioned additive does not include an acid. Examples of such an acid include organic acids such as acetic acid, propionic acid, and lactic acid, and lactic acid is particularly preferred.

[0173] Examples of the polymerization initiator and the crosslinking agent include the same polymerization initiator and the crosslinking agent as those which may be contained in the above-mentioned adhesive matrix material, and these may be used alone or in combination of two or more.

[0174] When the adhesive sheet of the present invention is a mixed adhesive sheet, the adhesive matrix material comprises a first polymerization initiator and a first cross-linking agent as a first initiator, the adhesive layer curing step is a curing based on the reaction of the first polymerization initiator and the first cross-linking agent, and the additive 11 is at least one selected from the group consisting of a second polymerization initiator and a second cross-linking agent as a second initiator.

[0175] After the adhesive layer curing step, sometimes both or either of the first polymerization initiator and the first crosslinking agent remain. In this case, only either the second polymerization initiator or the second crosslinking agent may be used as the additive 11. However, both the second polymerization initiator and the second crosslinking agent may also be used as the additive.

[0176] When the adhesive sheet of the present invention is a mixed adhesive sheet, the combination of the first initiator and the second initiator has a great degree of freedom. That is, the combination of polymerization initiators is not limited, and the combination of the first initiator and the second initiator can be freely selected, for example, the combination of the first initiator and the second initiator as photopolymerization initiators, the combination of the first initiator as a thermal polymerization initiator and the second initiator as a photopolymerization initiator, the combination of the first initiator as a photopolymerization initiator and the second initiator as a thermal polymerization initiator, etc., in addition, it can also be a combination of the first initiator and the second initiator as thermal polymerization initiators that is difficult to achieve in the previous mixed adhesive sheet. In addition, in the case where the first initiator and the second initiator are a combination of photopolymerization initiators, it can also be a situation where the light absorption wavelength bands of the two photopolymerization initiators overlap and are similar. Furthermore, as the first initiator and the second initiator that cannot be achieved in the previous mixed adhesive sheet, it can also be a combination of the same polymerization initiator (both thermal polymerization initiator and photopolymerization initiator).

[0177] Furthermore, the combination of crosslinking agents is not limited, and the first initiator and the second initiator may be a combination of the same crosslinking agent.

[0178] As the aforementioned ultraviolet absorber, there is no particular limitation, and examples thereof include triazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, oxybenzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, cyanoacrylate ultraviolet absorbers, etc., and one or more of them can be used alone or in combination. Among these, triazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, and benzophenone ultraviolet absorbers are preferred. From the aspect of good solubility and high ultraviolet absorption capacity near a wavelength of 380nm, at least one ultraviolet absorber selected from the group consisting of triazine ultraviolet absorbers having two or less hydroxyl groups in one molecule, benzotriazole ultraviolet absorbers having one benzotriazole skeleton in one molecule, and benzophenone ultraviolet absorbers is preferred.

[0179] Specific examples of the triazine-based ultraviolet absorber having two or less hydroxyl groups in one molecule include 2,4-bis-[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (Tinosorb S, manufactured by BASF), 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (TINUVIN460, manufactured by BASF), 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-hydroxyphenyl and [(C 10 -C 16 (Mainly C 12 -C 13)alkoxy)methyl] ethylene oxide reaction product (TINUVIN400, manufactured by BASF), 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol), reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis-(2,4-dimethylphenyl)-1,3,5-triazine and (2-ethylhexyl) glycidate (TINUVIN405, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol (TINUVIN1577, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]-phenol (ADK STAB LA46, manufactured by ADEKA Corporation), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (TINUVIN479, manufactured by BASF Corporation), and the like.

[0180] Examples of benzotriazole-based ultraviolet absorbers having one benzotriazole skeleton in one molecule include 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVIN PS, manufactured by BASF), phenylpropionic acid, and 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy(C 7-9side chain and straight chain alkyl) ester compound (TINUVIN384-2, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN900, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN928, manufactured by BASF), methyl-3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl) propionate / polyethylene glycol 300 reaction product (TINUVIN1130, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (TINUVIN P, BASF), 2-(2H-benzotriazol-2-yl)-4-6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN234, BASF), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN326, BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol (TINUVIN328, BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN TINUVIN329, manufactured by BASF), reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl) propionate and polyethylene glycol 300 (TINUVIN213, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (TINUVIN571, manufactured by BASF), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole (Sumisorb250, manufactured by Sumitomo Chemical Industries, Ltd.), etc.

[0181] Examples of the benzophenone-based ultraviolet absorbers (benzophenone-based compounds) and oxybenzophenone-based ultraviolet absorbers (oxybenzophenone-based compounds) include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (anhydride and trihydrate), 2-hydroxy-4-octyloxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 4-benzyloxy-2-hydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone (Seesorb 106, manufactured by SHIPRO KASEI Co., Ltd.), and 2,2'-dihydroxy-4,4-dimethoxybenzophenone.

[0182] Examples of the salicylate ultraviolet absorber (salicylate compound) include phenyl 2-acryloxybenzoate, phenyl 2-acryloxy-3-methylbenzoate, phenyl 2-acryloxy-4-methylbenzoate, phenyl 2-acryloxy-5-methylbenzoate, phenyl 2-acryloxy-3-methoxybenzoate, phenyl 2-hydroxybenzoate, phenyl 2-hydroxy-3-methylbenzoate, phenyl 2-hydroxy-4-methylbenzoate, phenyl 2-hydroxy-5-methylbenzoate, phenyl 2-hydroxy-3-methoxybenzoate, phenyl 3,5-di-tert-butyl-4-hydroxybenzoate (TINUVIN 120, manufactured by BASF).

[0183] Examples of the cyanoacrylate ultraviolet absorber (cyanoacrylate compound) include 2-cyanoacrylate alkyl esters, 2-cyanoacrylate cycloalkyl esters, 2-cyanoacrylate alkoxyalkyl esters, 2-cyanoacrylate alkenyl esters, and 2-cyanoacrylate alkynyl esters.

[0184] The maximum absorption wavelength of the absorption spectrum of the ultraviolet absorber is preferably present in the wavelength region of 300 to 400 nm, more preferably in the wavelength region of 320 to 380 nm. The maximum absorption wavelength refers to the absorption maximum wavelength showing the maximum absorbance among multiple maximum absorption maxima in the spectral absorption spectrum in the wavelength region of 300 to 460 nm.

[0185] When the additive is at least one selected from a polymerization initiator and a crosslinking agent, the additive preferably further comprises an ultraviolet absorber. By making the additive further comprise an ultraviolet absorber on the basis of comprising at least one selected from a polymerization initiator and a crosslinking agent, a mixed adhesive sheet comprising an ultraviolet absorber can be manufactured by a single coating, thereby improving manufacturing efficiency. In addition, if the mixed adhesive sheet comprising an ultraviolet absorber is irradiated with ultraviolet rays, the ultraviolet absorber that absorbs the ultraviolet rays generates heat and promotes the curing reaction, which can improve the bonding reliability, and is therefore more preferred.

[0186] The rust inhibitor is not particularly limited, and examples thereof include benzotriazole compounds, amine compounds, etc. In addition, examples thereof include ammonium benzoate, ammonium phthalate, ammonium stearate, ammonium palmitate, ammonium oleate, dicyclohexylamine benzoate, urea, hexamethylenetetramine, thiourea, phenyl carbamate, cyclohexyl ammonium-N-cyclohexyl carbamate (CHC), etc. It should be noted that the rust inhibitor may be used alone or in combination of two or more.

[0187] Examples of the benzotriazole compounds include benzotriazole (1,2,3-benzotriazole), 4-methylbenzotriazole, 5-methylbenzotriazole, 4-ethylbenzotriazole, 5-ethylbenzotriazole, 4-propylbenzotriazole, 5-propylbenzotriazole, 4-isopropylbenzotriazole, 5-isopropylbenzotriazole, 4-n-butylbenzotriazole, 5-n-butylbenzotriazole, 4-isobutylbenzotriazole, 5-isobutylbenzotriazole, 4-pentylbenzotriazole, 5-pentylbenzotriazole, 4-hexylbenzotriazole, and 5-hexylbenzotriazole; and alkyl groups having 1 to 6 carbon atoms. Benzotriazole; 5-methoxybenzotriazole, 1-hydroxybenzotriazole, 5-hydroxybenzotriazole, dihydroxypropylbenzotriazole, carboxybenzotriazole, 2,3-dicarboxypropylbenzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]benzotriazole, 1-[maleic acid]benzotriazole, 4-chlorobenzotriazole, 5-chlorobenzotriazole, 4-nitrobenzotriazole, 5-nitrobenzotriazole, benzotriazole monoethanolamine salt, benzotriazole diethylamine salt, benzotriazole cyclohexylamine salt, benzotriazole morpholine salt, benzotriazole isopropylamine salt, methylbenzotriazole cyclohexylamine salt, etc.

[0188] Examples of the amine compound include hydroxyl-containing amine compounds such as 2-amino-2-methyl-1-propanol, monoethanolamine, monoisopropanolamine, diethylethanolamine, ammonia, and ammonia water; cyclic amines such as morpholine; cyclic alkylamine compounds such as cyclohexylamine; and linear alkylamines such as 3-methoxypropylamine.

[0189] As the aforementioned antistatic agent, there is no particular limitation, and from the viewpoint of compatibility with acrylic polymers and transparency of the adhesive layer, it is preferably an ionic compound containing fluorinated anions. As the aforementioned ionic compound containing fluorinated anions, LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, etc. can be listed, preferably fluorinated lithium imide salts such as Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(FSO2)2N, particularly preferably bis(trifluoromethanesulfonyl)imide lithium salts, bis(fluorosulfonyl)imide lithium salts. It should be noted that the antistatic agent can be used alone or in combination of two or more.

[0190] The solvent is not particularly limited as long as it can dissolve the additive and swell the adhesive layer 10 a . Aqueous solvents are preferably non-aqueous solvents because aqueous solvents have poor wettability in the adhesive layer and the additives are less likely to penetrate. The non-aqueous solvent is not particularly limited, and examples thereof include esters such as methyl acetate, ethyl acetate, isopropyl acetate, and butyl acetate; aromatic hydrocarbons such as toluene, xylene, and ethylbenzene; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; alicyclic ketones such as cyclopentanone and cyclohexanone; aliphatic hydrocarbons such as hexane, heptane, and octane; alicyclic hydrocarbons such as cyclohexane; halogenated hydrocarbons such as chloroform, dichloromethane, and 1,2-dichloroethane; ethers such as diethyl ether, dimethoxyethane, tetrahydrofuran, and dioxane; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; nitriles such as acetonitrile, propionitrile, and benzonitrile; and alcohols such as methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, sec-butanol, and tert-butanol. Preferably, the solvent is an ester, an aromatic hydrocarbon, a ketone, or an alcohol. The solvent may be used alone or in combination of two or more.

[0191] The concentration of the above-mentioned additive in the solution can be appropriately set according to the desired required characteristics to be imparted to the adhesive layer 10a, and can be appropriately selected, for example, 95% by weight or less (for example, 0.1 to 95% by weight, 0.1 to 90% by weight, 0.1 to 85% by weight, 0.1 to 80% by weight, 0.1 to 70% by weight, 0.1 to 60% by weight, 0.1 to 50% by weight, 0.1 to 40% by weight, etc.), for example, 0.1% by weight or more (for example, 0.1 to 95% by weight, 0.2 to 95% by weight, 0.3 to 95% by weight, 0.4 to 95% by weight, 0.5 to 95% by weight, 1 to 95% by weight, 1.5 to 95% by weight, 3 to 95% by weight, 5 to 95% by weight, etc.). If the concentration of the additive in the solution is within this range, the additive can be dissolved, and the adhesive layer 10a can be fully swollen, thereby imparting appropriate required characteristics to the adhesive layer 10a.

[0192] Specifically, when the aforementioned additive is a cross-linking agent, the concentration of the cross-linking agent in the solution can be appropriately set according to the desired curing characteristics that should be imparted to the adhesive layer 10a, and can be appropriately selected from a range of, for example, less than 95 weight % (for example, 1 to 95 weight %, 1 to 90 weight %, 1 to 85 weight %, 1 to 80 weight %, 1 to 60 weight %, etc.), for example, more than 1 weight % (for example, 1 to 95 weight %, 2 to 95 weight %).

[0193] In addition, when the aforementioned additive is a UV absorber, the concentration of the UV absorber in the solution can be appropriately set according to the desired UV absorption characteristics that should be imparted to the adhesive layer 10a, and can be selected from a range with an upper limit of less than 50 weight % (for example, 1 to 50 weight %, 1 to 45 weight %, 1 to 40 weight %, 1 to 35 weight %, 1 to 30 weight %, 1 to 25 weight %, 1 to 20 weight %, 1 to 15 weight %, etc.) or a lower limit of more than 1 % (for example, 1 to 50 weight %, 2 to 50 weight %, 3 to 50 weight %, 4 to 50 weight %, 5 to 50 weight %).

[0194] In addition, when the aforementioned additive is a rust inhibitor, the concentration of the rust inhibitor in the solution can be appropriately set according to the desired rust-proof properties to be imparted to the adhesive layer 10a, and can be selected from a range with an upper limit of 10% by weight or less (e.g., 0.1 to 10% by weight, 0.1 to 9% by weight, 0.1 to 8% by weight, 0.1 to 7% by weight, 0.1 to 6% by weight, 0.1 to 5% by weight, 0.1 to 4% by weight, etc.) or a lower limit of 0.1% or more (e.g., 0.1 to 10% by weight, 0.2 to 10% by weight, 0.3 to 10% by weight, 0.4 to 10% by weight, 0.5 to 10% by weight).

[0195] In addition, when the aforementioned additive is an antistatic agent, the concentration of the antistatic agent in the solution can be appropriately set according to the desired antistatic properties that should be imparted to the adhesive layer 10a, and can be selected from a range with an upper limit of less than 95 weight % (for example, 0.1 to 90 weight %, 0.1 to 9 weight %, 0.1 to 85 weight %, 0.1 to 80 weight %, 0.1 to 75 weight %, 0.1 to 70 weight %, etc.) or a lower limit of more than 0.1 % (for example, 0.1 to 90 weight %, 0.2 to 90 weight %, 0.3 to 90 weight %, 0.4 to 90 weight %, 0.5 to 90 weight %, 0.6 to 90 weight %, 1 to 90 weight %, etc.).

[0196] If the concentration of each of the above additives (crosslinking agent, ultraviolet absorber, rust inhibitor, antistatic agent) is higher than the above range, the additives may ooze out or distribution deviation may occur from the viewpoint of coating uniformity. In addition, if the concentration is lower than the above range, the solvent needs to be more than the necessary amount, and the residual solvent may reduce the adhesive properties and swell the adhesive to a greater extent than necessary, thus sometimes causing poor appearance (surface unevenness) and the like.

[0197] The solution 12 may be applied (coated) to the adhesive layer 10a using a known coating method, such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a knife coater, a spray coater, a comma coater, a direct coater, or the like.

[0198] The coating amount of the solution of the additive on the adhesive layer 10a can be appropriately set according to the desired properties to be imparted to the adhesive layer 10a, and can be, for example, 1 to 1000 μg / cm 2 , preferably 1 to 500 μg / cm 2 , more preferably 1 to 300 μg / cm 2 , more preferably 1 to 100 μg / cm 2 When the coating amount of the solution of the additive is within this range, the additive can be dissolved and sufficient required properties can be imparted to the adhesive layer 10a.

[0199] After the solution of the additive is applied to the adhesive layer 10a, it can be left to stand as needed to allow the additive to penetrate. The standing time is not particularly limited, and can be appropriately selected from, for example, within 15 minutes, and can be selected from, for example, 1 second to 10 minutes, preferably from 5 seconds to 5 minutes. As the standing temperature, it can be carried out at room temperature (about 10 to 30°C). When standing under the above conditions, the additive can be fully impregnated into the adhesive layer 10a.

[0200] The heating and drying temperature in the drying step is preferably 40 to 200° C., more preferably 50 to 180° C., and further preferably 60 to 170° C. The drying time can be appropriately used for a suitable time, for example, 5 seconds to 20 minutes, preferably 5 seconds to 10 minutes, and more preferably 10 seconds to 5 minutes. By drying under the above conditions, the adhesive layer 10a can be restored to a state close to that before coating.

[0201] In addition, a standing time can be set as needed to make the additive and the adhesive layer more uniform. The standing time is not particularly limited, and can be appropriately selected from, for example, within 30 days, and can be appropriately selected from, for example, within 1 hour to 15 days, preferably within 24 hours to 10 days. By standing, the adhesive layer 10a can stabilize the additive and the adhesive layer, and can suppress the deviation of the characteristic evaluation.

[0202] Figure 2 (a) is a cross-sectional view showing one embodiment of the adhesive sheet according to the third aspect of the present invention, Figure 2 (b) is a cross-sectional view showing another embodiment of the adhesive sheet according to the third aspect of the present invention.

[0203] If you refer to Figure 2 (a), then an adhesive sheet 2A of one embodiment of the present invention is composed of an optically transparent adhesive layer 21 and a support body S1, the support body is not adhered to a first main surface 21a of the adhesive layer 21, but is adhered to another second main surface 21b of the adhesive layer 21, and the support body S1 is formed by a peeling sheet.

[0204] If you refer to Figure 2 (b), then an adhesive sheet 2B of one embodiment of the present invention is composed of an optically transparent adhesive layer 21, a first support S2 and a second support S1, wherein the first support S2 is bonded to a first main surface 21a of the adhesive layer 21 and is formed by a release sheet, and the second support S1 is bonded to the other second main surface 21b of the adhesive layer 21 and is formed by a release sheet. The adhesive sheet 2B can be obtained by bonding the support S2 to the first main surface 21a of the adhesive sheet 2A.

[0205] exist Figure 2 In (a) and (b), the dashed line XX' is a line segment that divides the adhesive layer 21 into two equal parts along the thickness direction. When the thickness of the adhesive layer 21 is uneven, the dashed line XX' is a line segment that divides the thickness at each point into two equal parts.

[0206] exist Figure 2 In the embodiment, the adhesive layer 21 is formed of a transparent adhesive matrix material and is a single layer having two opposite main surfaces (a first main surface and a second main surface). The adhesive layer 21 can be formed by the above-mentioned adhesive layer forming step and adhesive layer curing step, which is equivalent to Figure 1 Therefore, the adhesive layer 21 is preferably a cured adhesive layer.

[0207] The adhesive layer being a "single layer" means that it is not a laminated structure. For example, an adhesive layer formed of a transparent adhesive matrix material is formed, and an adhesive layer formed of the same transparent adhesive matrix material is formed thereon to obtain a laminated structure, not a single layer. Similarly, an adhesive layer formed of a transparent adhesive matrix material in which an additive is dissolved is formed, and an adhesive layer formed of a transparent adhesive matrix material in which an additive is dissolved at a different concentration is formed thereon to obtain a laminated structure, not a single layer.

[0208] The thickness of the adhesive layer 21 is not particularly limited, but is generally 5 to 500 μm, preferably 5 to 400 μm, and more preferably 5 to 350 μm. If the thickness of the adhesive layer 21 is within this range, it is suitable for forming a concentration gradient of the additive along the thickness direction of the adhesive layer 21 .

[0209] The total light transmittance of the adhesive layer 21 as a whole is not particularly limited, but is preferably 80% or more, preferably 90% or more, as measured in accordance with JIS K7361. The higher the total light transmittance of the adhesive layer 21, the more preferred. In addition, the haze value is preferably 1.5% or less, more preferably 1% or less.

[0210] The additive 11 is dissolved in the adhesive layer 21. Here, "dissolved" means, for example, that the additive is dissolved to the extent that the transparency of the adhesive layer can be maintained, that is, the degree to which white turbidity caused by light scattering of the additive does not occur. Specifically, it is preferred that the additive is included in the adhesive layer in such a manner that the haze value of the adhesive layer is 1.5% or less, preferably 1% or less.

[0211] The additive 11 is formed by impregnating the adhesive layer 21 with the additive 11 through the aforementioned solution coating process, solution penetration process, and drying process. Figure 2 As shown in FIG. 1 , a concentration gradient of the additive 11 can be generated along the thickness direction of the adhesive layer 21. Therefore, when the single-layer adhesive layer 21 is divided into two equal parts along the thickness direction, the concentration of the additive in the region to which the first main surface 21a belongs, one of the two main surfaces, is different from the concentration of the additive in the region to which the other main surface 21b belongs. The case where the additive does not exist in the region where the concentration of the additive is low (the concentration of the additive is 0) is also included in the scope of the present invention.

[0212] When there are concentration gradients in the respective regions, the concentration of the additive in the region to which the first main surface belongs and the concentration of the additive in the region to which the second main surface belongs refer to average concentrations of the additive in the respective regions.

[0213] Figure 2 (a) is an embodiment in which the second main surface 21b faces the supporting body S1, and the concentration of the additive in the area to which the first main surface 21a belongs is higher than the concentration of the additive in the area to which the second main surface 21b belongs, and the embodiment can be obtained by applying a solution of the additive on the first main surface 21a and allowing the additive to penetrate into the adhesive layer 21 from the first main surface 21a throughout the depth in the thickness direction in a state in which the additive is dissolved.

[0214] In the adhesive sheet of the third aspect of the present invention, Figure 2 As shown in the figure, by distributing additives such as rust inhibitors and antistatic agents at high concentrations near the first main surface 21a, the first main surface 21a can be given the required characteristics such as rust prevention and antistatic functions achieved by the additives. On the other hand, since the concentration of the additive 11 in the entire adhesive layer 21 can be reduced, the change in the physical properties of the adhesive layer 21 caused by the additive 11 can be reduced.

[0215] The adhesive sheet of the third aspect of the present invention can be used to join transparent optical components to other optical components in image display devices such as liquid crystal image display devices and organic EL image display devices. As the aforementioned optical components, transparent cover components such as polarizing films, phase difference films, and cover glasses, and other various transparent optical components can be listed. In addition, a glass substrate formed with a transparent conductive layer such as a patterned ITO film is also included in the optical component of the present invention. In addition, the adhesive sheet of the third aspect of the present invention can also be suitably used as a surface protection film for preventing the aforementioned optical components from being damaged or dirt from adhering.

[0216] Figure 3 This is a cross-sectional view of an optical member laminate showing an example of the simplest embodiment using the adhesive sheet of the present invention. Figure 3 , the optical member stack 3 is composed of an optically transparent first optical member 31 and a second optical member 32, and the second optical member 32 is bonded to the first optical member 31 via an optically transparent adhesive layer 21. The optical member stack 3 is Figure 2 The first optical member 31 and the second optical member 32 are obtained by peeling off the support bodies S1 and S2 from the adhesive sheet 2B shown in (b) and bonding them to the first optical member 31 and the second optical member 32. The transparent first optical member 31 and the second optical member 32 can be composed of a polarizing film, a phase difference film, other optical films used in an optical display device, and a transparent cover member such as a cover glass on the identification side of an optical display device. The first optical member 31 is bonded to the first main surface 21a of the adhesive layer 21, and the second optical member 32 is bonded to the second main surface 21b of the adhesive layer 21.

[0217] Figure 4 Schematically shows the process of one embodiment of the method for manufacturing an optical member stack according to the second aspect of the present invention. Figure 4 As shown in (a) of FIG. 1 , an adhesive sheet 2C and a substrate 42 formed of an optical member (hereinafter, sometimes simply referred to as “substrate 42 ”) are used.

[0218] In the present embodiment, the adhesive sheet 2C is produced by the method for producing the adhesive sheet according to the first aspect of the present invention, which is a hybrid adhesive sheet. Specifically, the adhesive sheet 2C is produced by the following method.

[0219] forming an adhesive layer on a support, the adhesive layer being formed of a transparent adhesive matrix material containing a first polymerization initiator and a first cross-linking agent;

[0220] curing the adhesive layer by utilizing the reaction of the first polymerization initiator and the first cross-linking agent;

[0221] preparing a solution of at least one additive selected from the group consisting of a second polymerization initiator and a second cross-linking agent;

[0222] Applying the solution on one surface of the cured adhesive layer, so that the additive contained in the solution penetrates from the one surface of the adhesive layer along the thickness direction;

[0223] The adhesive layer is dried.

[0224] for Figure 4 As for the adhesive sheet 2C of (a), in the present embodiment, the adhesive layer 41 is obtained by curing the reaction of the first polymerization initiator and the first crosslinking agent (not shown), and the second polymerization initiator 11a and the second crosslinking agent 11b are dispersed in a dissolved state. The present invention also includes a method in which only one of the second polymerization initiator 11a and the second crosslinking agent 11b is dissolved in the adhesive layer 41.

[0225] In this embodiment, the adhesive sheet 2C has the support S3, but may not have the support S3. In this embodiment, the concentration gradient of the second polymerization initiator 11a and the second crosslinking agent 11b exists along the thickness direction from the main surface 41a of the adhesive layer 41 in contact with the support S3.

[0226] for Figure 4 In the present embodiment, the main surface 42a bonded to the adhesive sheet 2C has a printed layer 43. The printed layer 43 may include a transparent and conductive printed layer such as patterned ITO (indium tin oxide), a black shielding portion formed in a frame shape at the edge of a transparent cover member, etc. The case of using a substrate 42 without a printed layer 43 is also included in the present invention.

[0227] Next, the adhesive layer 41 of the adhesive sheet 2C is bonded to the main surface 42a of the substrate 42. The bonding can be performed using a known method, for example, using heating and pressurizing conditions using an autoclave. The adhesive layer 41 of the adhesive sheet 2C is obtained by curing the reaction of the aforementioned first polymerization initiator and the first crosslinking agent (first initiator), and is in a state before the curing reaction based on at least one (second initiator) selected from the group consisting of the second polymerization initiator 11a and the second crosslinking agent 11b, and has high fluidity and shows excellent height difference absorption. Therefore, the adhesive layer 41 is bonded in a manner that fills the height difference between the main surface 42a of the substrate 42 and the printed layer 43 without a gap.

[0228] Next, the adhesive layer 41 is cured by a reaction of at least one (second initiator) selected from the group consisting of the second polymerization initiator 11a and the second crosslinking agent 11b. The method for curing the adhesive layer 41 is not particularly limited as long as the curing reaction is carried out using the second initiator, and examples thereof include heating the adhesive layer 41; curing the adhesive layer 41 by irradiating active energy rays. Further heating and drying may be performed as required. Examples of active energy rays include ionizing radiation such as α rays, β rays, γ rays, neutron rays, electron rays, and ultraviolet rays, and ultraviolet rays are particularly preferred.

[0229] The conditions for curing the adhesive layer 41 may be such that, for example, the heating temperature, time, or the irradiation amount of active energy rays is appropriately set so that the adhesive layer 41 exhibits a high elastic modulus and excellent adhesive reliability.

[0230] Figure 4 (c) is an embodiment of curing the adhesive layer 41 by irradiating the adhesive layer 41 with ultraviolet rays U. The second polymerization initiator 11a is decomposed by irradiating the ultraviolet rays U to generate free radicals or ions, thereby initiating a polymerization / crosslinking reaction of the second crosslinking agent 11b. The ultraviolet rays may be irradiated directly to the adhesive layer 41 or through the support S3. Figure 4 (c) is an embodiment in which the adhesive layer 41 is irradiated with ultraviolet rays U via the support S3. When the adhesive layer 41 is directly irradiated with ultraviolet rays, the ultraviolet rays U may be irradiated after the support S3 is peeled off from the adhesive layer 41.

[0231] By curing the adhesive layer 41, Figure 4 As shown in (d) of FIG. , an optical member stack 4 can be obtained. Figure 4 In (d), 41c is a pressure-sensitive adhesive layer obtained by curing the pressure-sensitive adhesive layer 41. The optical member stacked body 4 is an embodiment showing an example of the optical member stacked body according to the fourth aspect of the present invention.

[0232] By curing the adhesive layer 41, the crosslinking agent 11b is crosslinked / polymerized to form a crosslinked structure 11c, thereby forming an adhesive layer 41c. The elastic modulus of the adhesive layer 41c is improved, and the bonding reliability with respect to the substrate 42 is improved. Therefore, the adhesive layer 41c suppresses the generation of gas such as carbon dioxide due to heating of the substrate 42 (plastic film), and prevents the generation of bubbles.

[0233] in addition, Figure 4In the embodiment (d), the crosslinking density of the side of the main surface 41a of the adhesive layer 41c in contact with the support body S3 is higher than that of the main surface 41b on the opposite side. This configuration is preferred from the viewpoint of being able to improve the bendability when, for example, the optical component stack 4 is used as a flexible image display device that bends one side of the main surface 41a outward.

[0234] That is, when the flexible display is bent, tensile stress is usually applied to the outside and compressive stress is applied to the inside, and the stress on the outside is stronger than the stress on the inside. Therefore, by arranging the main surface 41a of the adhesive layer 41c on the outside when the flexible display is bent, the durability against bending can be improved.

[0235] In this embodiment, the optical member stacked body 4 has the following structure, for example.

[0236] An optical member stack 4 includes a substrate 42 formed of an optical member and an adhesive layer 41c,

[0237] The adhesive layer 41c is laminated on the main surface of the substrate 43 formed of the optical member.

[0238] The adhesive layer 41c is formed of a transparent adhesive matrix material cured by a reaction of the first polymerization initiator and the first crosslinking agent (first initiator) and a reaction of at least one selected from the group consisting of the second polymerization initiator 11a and the second crosslinking agent 11b (second initiator), and is a single layer having two opposing main surfaces.

[0239] When the above-mentioned single-layer adhesive layer is divided into two equal parts along the thickness direction,

[0240] The density of the cross-linked structure 11 c in the region to which the first main surface 41 a belongs, which is one of the two main surfaces, is different from the density of the cross-linked structure 11 c in the region to which the other main surface 41 b belongs.

[0241] In the present embodiment, the adhesive layer 41 c is laminated so as to fill the height difference between the main surface 42 a of the substrate 42 and the printed layer 43 .

[0242] Example

[0243] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples.

[0244] (Preparation of Adhesive Sheet A)

[0245] To a monomer mixture consisting of 66 parts by weight of 2-ethylhexyl acrylate (2EHA), 19 parts by weight of 2-hydroxyethyl acrylate (HEA) and 15 parts by weight of N-vinyl-2-pyrrolidone (NVP) were added 0.035 parts by weight of a photopolymerization initiator (trade name "Irgacure 184", manufactured by BASF) and 0.035 parts by weight of a photopolymerization initiator (trade name "Irgacure 651", manufactured by BASF), and then irradiated with ultraviolet rays until the viscosity (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature: 30°C) reached about 20 Pa·s, thereby obtaining a prepolymer composition in which part of the above-mentioned monomer components was polymerized.

[0246] Next, 0.2 parts by weight of hexanediol diacrylate (HDDA) was added to the prepolymer composition and mixed to obtain an acrylic adhesive composition. The acrylic adhesive composition was applied to the peeling-treated surface of a release film (trade name "MRF#38", manufactured by Mitsubishi Resins) in such a manner that the thickness of the adhesive layer formed was 100 μm to form an adhesive composition layer. Next, a release film (trade name "MRN#38", manufactured by Mitsubishi Resins) was attached to the surface of the adhesive composition layer. Thereafter, the adhesive composition was subjected to an irradiation of 5 mW / cm 2 , Light intensity: 1500mJ / cm 2 The adhesive composition layer is photocured by ultraviolet irradiation under conditions of , to form an adhesive sheet A.

[0247] (Preparation of Adhesive Sheet B)

[0248] An adhesive sheet B was formed in the same manner as the adhesive sheet A except that the added amount of hexanediol diacrylate (HDDA) was changed to 0.1 parts by weight.

[0249] (Preparation of Adhesive Sheet C)

[0250] Adhesive sheet C was formed by the same operation as Adhesive sheet A except that 96 parts by weight of butyl acrylate (BA) and 4 parts by weight of acrylic acid (AA) were used as the monomer mixture, and 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) was used instead of hexanediol diacrylate (HDDA). The thickness of the adhesive layer after formation was set to 23 μm.

[0251] (Preparation of Adhesive Sheet D)

[0252] As the monomer mixture, 57 parts by weight of butyl acrylate (BA), 23 parts by weight of 4-hydroxybutyl acrylate (4HBA), 8 parts by weight of 2-hydroxyethyl acrylate (HEA) and 12 parts by weight of cyclohexyl acrylate (CHA) were used, and 0.02 parts by weight of dipentaerythritol hexaacrylate (DPHA) was used instead of hexanediol diacrylate (HDDA). The thickness of the adhesive layer after formation was set to 150 μm. Except for this, the same operation as adhesive sheet A was performed to form adhesive sheet D.

[0253] (Preparation of Adhesive Sheet E)

[0254] Adhesive sheet E was formed in the same manner as Adhesive sheet A except that 29 parts by weight of 2-ethylhexyl acrylate (2EHA), 21 parts by weight of 4-hydroxybutyl acrylate (4HBA), 29 parts by weight of isostearyl acrylate (ISTA), and 21 parts by weight of isobornyl acrylate (IBXA) were used as the monomer mixture.

[0255] (Preparation of Adhesive Sheet F)

[0256] As the monomer mixture, 41 parts by weight of 2-ethylhexyl acrylate (2EHA), 1 part by weight of 4-hydroxybutyl acrylate (4HBA), 17 parts by weight of N-vinyl-2-pyrrolidone (NVP) and 41 parts by weight of isostearyl acrylate (ISTA) were used, and 0.02 parts by weight of trimethylolpropane triacrylate (TMPTA) was used instead of hexanediol diacrylate (HDDA). Except for this, the same operation as that of adhesive sheet A was carried out to form adhesive sheet F.

[0257] (Preparation of Adhesive Sheet G)

[0258] As the monomer mixture, 57 parts by weight of butyl acrylate (BA), 23 parts by weight of 4-hydroxybutyl acrylate (4HBA), 8 parts by weight of 2-hydroxyethyl acrylate (HEA) and 12 parts by weight of cyclohexyl acrylate (CHA) were used, and 0.03 parts by weight of dipentaerythritol hexaacrylate (HEA) was used instead of hexanediol diacrylate (HDDA). The thickness of the adhesive layer after formation was set to 250 μm. Except for this, the same operation as adhesive sheet A was performed to form adhesive sheet G.

[0259] (Example 1)

[0260] The release film on one main surface (referred to as the "first surface") of the adhesive sheet A was peeled off, and a 10 wt% ethyl acetate solution of a UV absorber (TinosorbS, manufactured by BASF) was applied to the exposed first surface using a Wire Wound Rod type, No. 7 rod coater manufactured by RD Specialties (target wet coating thickness was 15 μm). After coating, the adhesive sheet A was heated and dried in an oven at 110° C. for 2 minutes to volatilize and remove the solvent, thereby obtaining an adhesive sheet A including an adhesive layer in which the UV absorber was dissolved.

[0261] (Comparative Example 1)

[0262] The release film on the first surface of the adhesive sheet A was peeled off, and the adhesive sheet A on which the ultraviolet absorber solution was not applied was used as Comparative Example 1.

[0263] (Example 2)

[0264] Using the adhesive sheet B, except that a 12 wt % ethyl acetate solution of an ultraviolet absorber (Tinuvin 928, manufactured by BASF) was applied, the same operation as in Example 1 was performed to obtain an adhesive sheet B including an adhesive layer in which the ultraviolet absorber was dissolved.

[0265] (Example 3)

[0266] The same procedure as in Example 1 was carried out except that a 12 wt % methyl ethyl ketone solution of an ultraviolet absorber (Tinuvin 928, manufactured by BASF) was applied to the adhesive sheet B to obtain an adhesive layer B in which the ultraviolet absorber was dissolved.

[0267] (Example 4)

[0268] The same procedures as in Example 1 were carried out except that a 15 wt % ethyl acetate solution of a UV absorber (Seesorb 106, manufactured by SHIPRO KASEI) was applied to the adhesive sheet B to obtain an adhesive sheet B including an adhesive layer in which the UV absorber was dissolved.

[0269] (Comparative Example 2)

[0270] The release film on the first surface of the adhesive sheet B was peeled off, and the adhesive sheet B on which the ultraviolet absorber solution was not applied was used as Comparative Example 2.

[0271] (Example 5)

[0272] A pressure-sensitive adhesive sheet C including a pressure-sensitive adhesive layer in which a UV absorber (Tinosorb S, manufactured by BASF) was dissolved was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive sheet C was used.

[0273] (Example 6)

[0274] Using the adhesive sheet C, except that an ethyl acetate solution having a concentration of 12 wt % of an ultraviolet absorber (Tinuvin 928, manufactured by BASF) was applied, the same procedures as in Example 1 were carried out to obtain an adhesive sheet C including an adhesive layer in which an ultraviolet absorber was dissolved.

[0275] (Example 7)

[0276] Using the adhesive sheet C, except that a 12 wt % methyl ethyl ketone solution of an ultraviolet absorber (Tinuvin 928, manufactured by BASF) was applied, the same procedures as in Example 1 were carried out to obtain an adhesive sheet C including an adhesive layer in which an ultraviolet absorber was dissolved.

[0277] (Example 8)

[0278] The same procedures as in Example 1 were carried out except that a 15 wt % ethyl acetate solution of a UV absorber (Seesorb 106, manufactured by SHIPRO KASEI) was applied to the adhesive sheet C to obtain an adhesive sheet C including an adhesive layer in which the UV absorber was dissolved.

[0279] (Comparative Example 3)

[0280] The release film on the first surface of the adhesive sheet C was peeled off, and the adhesive sheet C on which the ultraviolet absorber solution was not applied was used as Comparative Example 3.

[0281] (Comparative Example 4)

[0282] Using the adhesive sheet C, except that ethyl acetate containing no ultraviolet absorber was applied, the same operation as in Example 1 was carried out to obtain an adhesive sheet C containing no ultraviolet absorber.

[0283] (Example 9)

[0284] A PSA sheet D including a PSA layer in which a UV absorber (Tinosorb S, manufactured by BASF) was dissolved was obtained in the same manner as in Example 1 except that the PSA sheet D was used.

[0285] (Comparative Example 5)

[0286] The release film on the first surface of the pressure-sensitive adhesive sheet D was peeled off, and the pressure-sensitive adhesive sheet D on which the ultraviolet absorber solution was not applied was used as Comparative Example 5.

[0287] (Example 10)

[0288] A PSA sheet E including a PSA layer in which a UV absorber (Tinosorb S, manufactured by BASF) was dissolved was obtained in the same manner as in Example 1 except that the PSA sheet E was used.

[0289] (Comparative Example 6)

[0290] The release film on the first surface of the adhesive sheet F was peeled off, and an adhesive sheet E on which the ultraviolet absorber solution was not applied was used as Comparative Example 6.

[0291] (Example 11)

[0292] A pressure-sensitive adhesive sheet F including a pressure-sensitive adhesive layer in which a UV absorber (Tinosorb S, manufactured by BASF) was dissolved was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive sheet F was used.

[0293] (Comparative Example 7)

[0294] The release film on the first surface of the pressure-sensitive adhesive sheet F was peeled off, and the pressure-sensitive adhesive sheet F on which the ultraviolet absorber solution was not applied was used as Comparative Example 7.

[0295] (Comparative Example 8)

[0296] Using the adhesive sheet F, except that ethyl acetate containing no ultraviolet absorber was applied, the same operation as in Example 1 was carried out to obtain an adhesive sheet F containing no ultraviolet absorber.

[0297] (Comparative Example 9)

[0298] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer in which the pressure-sensitive adhesive layer was uniformly dissolved was obtained in the same manner as in pressure-sensitive adhesive sheet D, except that 70 parts by weight of butyl acrylate (BA), 14 parts by weight of 4-hydroxybutyl acrylate (4HBA), and 16 parts by weight of N-vinyl-2-pyrrolidone (NVP) were used as the monomer mixture, and 0.0009 parts by weight of a UV absorber (Tinosorb S, manufactured by BASF) was further added to the acrylic pressure-sensitive adhesive composition.

[0299] <Transmittance Evaluation>

[0300] The release films of the adhesive sheets obtained in Examples 1 to 11 and Comparative Examples 1 to 8 were peeled off, and the transmittance at each light wavelength (wavelength range: 300 to 800 nm) was evaluated using a spectrophotometer (U4100, manufactured by Hitachi High-Technologies Corporation).

[0301] <Adhesion Evaluation>

[0302] The release films of the adhesive sheets obtained in Examples 1 to 11 and Comparative Examples 1 to 8 were peeled off. The surface coated with the ultraviolet absorber solution was made the first surface, and the opposite main surface was made the second surface.

[0303] The obtained adhesive sheet was cut into 100 mm wide and 100 mm long, and the first or second side was bonded to the alkali glass, and a PET film (thickness: 25 μm) was bonded to the reverse side, and bonded using a manual roller, and heated and pressurized in an autoclave (5 atm, 50°C) for 15 minutes. The adhesive strength (N / 10mm) of the sample obtained by the above operation was measured using AUTOGRAPH (tensile speed: 60 mm / min. Peeling angle: 180°). In the measurement, 3 samples were made for each condition, and their number average was taken. The adhesive strength (N / 10mm) of the first and second sides relative to the alkali glass and their difference are shown in Table 1.

[0304] [Table 1]

[0305]

[0306] It is clear from Table 1 that by applying a solution of an ultraviolet absorber on the adhesive layer of the adhesive sheet cured by ultraviolet rays, it is possible to impart excellent ultraviolet absorption function to the adhesive layer. It is also known that by setting the difference in adhesive force between the first side and the second side of the adhesive layer to 1.0 N / mm and applying a solution of an ultraviolet absorber on the adhesive layer of the cured adhesive sheet, it is possible to minimize the difference in physical properties such as adhesive force between the front and back sides of the adhesive layer.

[0307] <Evaluation of Distribution of Ultraviolet Absorber in the Thickness Direction of Adhesive>

[0308] TOF-SIMS analysis (Ar gas cluster ion etching method) was performed to examine the distribution state of the ultraviolet absorber (Tinosorb S) in the thickness direction of Example 9 and Comparative Example 9. Samples stored for one month after production were used.

[0309] The release films of the adhesive sheets obtained in Example 9 and Comparative Example 9 were peeled off, and TOF-SIMS analysis was performed from the first surface side under the following measurement conditions. The results are shown in FIG. Figure 5 . Figure 5 (a) is the result of Example 9, Figure 5 (b) is the result of Comparative Example 9. Figure 5 In the figure, the scale of the left vertical axis represents the intensity of butyl acrylate (BA, C3+H3+O2) and N-vinyl pyrrolidone (NVP, C4+H6+N+O), and the scale of the right vertical axis represents the intensity of ultraviolet absorber (Tinosorb S, C 30 +H 32+N3+O5) intensity.

[0310] Analysis device: TOF-SIMS (ULVAC-PHI, TRIFT V)

[0311] Etching ions: Ar gas cluster ions

[0312] Irradiated primary ion: Bi3 2+

[0313] Accelerating voltage: 30 kV

[0314] Determination of polarity: negative ions

[0315] according to Figure 5 (a) shows that the adhesive layer of the adhesive sheet of Example 9 has a concentration gradient of the ultraviolet absorber (Tinosorb S) from the first surface to the second surface. Figure 5 (b) shows that the ultraviolet absorber (Tinosorb S) is distributed at a constant concentration from the first surface to the second surface of the adhesive layer of the adhesive sheet of Comparative Example 9.

[0316] (Example 12)

[0317] The release film on one main surface (referred to as the "first surface") of the adhesive sheet A was peeled off, and an ethyl acetate solution (target wet coating thickness: 15 μm) obtained by diluting hexanediol diacrylate (HDDA) to a concentration of 20 wt% and diluting a photopolymerization initiator (Omnirad 184, manufactured by IGM Resins BV) to a concentration of 1 wt% was applied to the exposed first surface using a wire wound rod type, No. 7 bar coater manufactured by RD Specialties. After coating, the adhesive sheet A was heated and dried in an oven at 110° C. for 2 minutes to volatilize and remove the solvent, thereby obtaining an adhesive sheet A including an adhesive layer in which HDDA was dissolved.

[0318] (Example 13)

[0319] A PSA sheet B including a PSA layer in which HDDA was dissolved was obtained in the same manner as in Example 12 except that the PSA sheet B was used.

[0320] (Example 14)

[0321] Using the adhesive sheet G, the same operation as in Example 12 was performed except that dipentaerythritol hexaacrylate (DPHA) was diluted to a concentration of 5 wt% and a photopolymerization initiator (Omnirad 184, manufactured by IGM Resins BV) was diluted to a concentration of 0.25 wt% to obtain an adhesive sheet G including an adhesive layer in which DPHA was dissolved.

[0322] (Example 15)

[0323] Using the adhesive sheet G, the same operation as in Example 12 was carried out except that hexanediol diacrylate (HDDA) was diluted to a concentration of 2 wt% and a photopolymerization initiator (Omnirad 184, manufactured by IGM Resins BV) was diluted to a concentration of 0.1 wt% to obtain an adhesive sheet G including an adhesive layer in which HDDA was dissolved.

[0324] (Example 16)

[0325] Using the adhesive sheet G, the same operation as in Example 12 was carried out except that an ethyl acetate solution having a concentration of 40 wt % of hexanediol diacrylate (HDDA) and a concentration of 2 wt % of a photopolymerization initiator (Omnirad 184, manufactured by IGM Resins BV) was applied, thereby obtaining an adhesive sheet G including an adhesive layer in which HDDA was dissolved.

[0326] (Example 17)

[0327] Using the adhesive sheet G, the same operation as in Example 12 was carried out except that an ethyl acetate solution having a concentration of 5 wt % of trimethylolpropane triacrylate (TMPTA) and a concentration of 0.25 wt % of the photopolymerization initiator Omnirad 184 (manufactured by IGM Resins BV) was applied to obtain an adhesive sheet G including an adhesive layer in which TMPTA was dissolved.

[0328] <Elastic modulus evaluation>

[0329] The release films of the adhesive sheets obtained in Examples 12 to 17 were peeled off, and an adhesive layer was laminated to a thickness of about 2 mm to prepare a measurement sample. Dynamic viscoelasticity was measured under the following conditions using the Advanced Rheometric Expansion System (ARES) manufactured by Rheometric Scientific.

[0330] (Measurement conditions)

[0331] Deformation mode: Twist

[0332] Measuring frequency: 1Hz

[0333] Heating rate: 5℃ / min

[0334] Shape: Parallel plate 7.9mmφ

[0335] Next, at an illumination of 300 mW / cm 2 、The accumulated light intensity is 3000mJ / cm 2 The above-mentioned sample for measurement was irradiated with ultraviolet rays under the conditions of , and cured, and the dynamic viscoelasticity was measured by the above-mentioned method. Table 2 shows the storage modulus at 85° C. before and after curing.

[0336] [Table 2]

[0337]

[0338] In Examples 12 to 17, the storage modulus was improved by providing curing conditions to the adhesive sheets A, B, and G obtained by coating the crosslinking agent solution on the adhesive layer and drying. Therefore, it can be seen that the adhesive sheets of Examples 12 to 17 are useful as mixed adhesive sheets. In addition, according to Examples 15 and 16, it can be seen that the storage modulus after curing can be controlled by adjusting the concentration of the crosslinking agent solution.

[0339] (Example 18)

[0340] The release film on one main surface (referred to as the "first surface") of the adhesive sheet C was peeled off, and a 0.5 wt% ethanol solution of a rust inhibitor (1,2,3-benzotriazole) was applied to the exposed first surface using a #7 rod coater of the Wire Wound Rod type manufactured by RD Specialties (target wet coating thickness was 15 μm). After coating, the adhesive sheet C was heated and dried in an oven at 110° C. for 2 minutes to volatilize and remove the solvent, thereby obtaining an adhesive sheet C including an adhesive layer in which the rust inhibitor was dissolved.

[0341] (Comparative Example 10)

[0342] The release film on the first surface of the adhesive sheet C was peeled off, and the adhesive sheet C on which the rust inhibitor solution was not applied was used as Comparative Example 10.

[0343] <Evaluation of rust prevention function>

[0344] The release film of the adhesive sheet obtained in Example 18 and Comparative Example 10 was peeled off. The surface coated with the rust inhibitor solution was made the first surface, and the opposite main surface was made the second surface. The obtained adhesive sheet was cut into 100 mm wide and 100 mm long, and the first surface or the second surface was attached to the copper-bearing film, and a PET film (thickness: 25 μm) was attached to the reverse surface, and attached by a hand roller, and heated and pressurized (5 atm, 50° C.) in an autoclave for 15 minutes. The copper-bearing film used was a film obtained by forming a hard coating on both sides of a cycloolefin film (trade name "ZEONOR (registered trademark) ZF16, thickness 50 μm), and forming a 50 nm copper layer on one side of the obtained product by sputtering (surface resistance value: 0.58 Ω / □). The film was stored in an environment of 85°C and 85% RH for 500 hours, and the state of the copper was evaluated before and after storage. The surface resistance value of the copper was measured using a cavity curing measuring device (AccentOptical Technologies, HL5500PC). In addition, the copper surface was visually observed to evaluate the presence or absence of corrosion. In addition, after storage, it was confirmed using a microscope whether the rust inhibitor was detected. The results are shown in Table 3.

[0345] [Table 3]

[0346] (Table 3)

[0347]

[0348] Table 3 shows that by applying the rust inhibitor solution on the adhesive layer, the adhesive layer can be given a rust-proof function. It also suggests that the surface resistance of the first surface coated with the rust inhibitor solution after 500 hours is lower than that of the second surface, and there is a difference in the concentration of the rust inhibitor between the front and back surfaces.

[0349] (Example 19)

[0350] The release film on one main surface (referred to as the "first surface") of the adhesive sheet C was peeled off, and an antistatic agent (lithium bis(trifluoromethanesulfonyl)imide) solution with a concentration of 5% by weight in ethanol (target wet coating thickness of 15 μm) was applied to the exposed first surface using a wire wound rod type, No. 7 rod coater manufactured by RD Specialties. After coating, the adhesive sheet C was heated and dried in an oven at 110° C. for 2 minutes to volatilize and remove the solvent, thereby obtaining an adhesive sheet C including an adhesive layer in which the antistatic agent was dissolved.

[0351] (Example 20)

[0352] A PSA sheet C including a PSA layer in which an antistatic agent was dissolved was obtained in the same manner as in Example 19 except that the concentration of the antistatic agent solution was changed to 10% by weight.

[0353] (Example 21)

[0354] A PSA sheet C including a PSA layer in which an antistatic agent was dissolved was obtained in the same manner as in Example 19 except that the concentration of the antistatic agent solution was changed to 20% by weight.

[0355] (Comparative Example 11)

[0356] The release film on the first surface of the PSA sheet C was peeled off, and the PSA sheet C on which the antistatic agent solution was not applied was used as Comparative Example 11.

[0357] <Evaluation of antistatic function>

[0358] One release film of the adhesive sheet obtained in Examples 19 to 21 and Comparative Example 11 was peeled off, and the surface resistance of the adhesive layer was measured under the following conditions. The main surface coated with the antistatic agent solution was referred to as the first surface, and the opposite main surface was referred to as the second surface. The results are shown in Table 4.

[0359] Measuring device: Hiresta MCP-HT450 (Mitsubishi Chemical Analytics)

[0360] Probe: URS

[0361] Applied voltage: 250V

[0362] [Table 4]

[0363] (Table 4)

[0364]

[0365] OVER:10 12 Ω or more

[0366] Table 4 shows that the antistatic function can be imparted to the pressure-sensitive adhesive by applying the antistatic agent solution on the pressure-sensitive adhesive layer.

[0367] (Example 22)

[0368] The release film on one main surface (referred to as the "first surface") of the adhesive sheet B was peeled off, and an ethyl acetate solution (target wet coating thickness of 15 μm) obtained by diluting a UV absorber (Tinosorb S, manufactured by BASF) to a concentration of 10 wt%, hexanediol diacrylate (HDDA) to a concentration of 20 wt%, and a photopolymerization initiator (Omnirad 819, manufactured by IGM Resins BV) to a concentration of 0.3 wt% was applied to the exposed first surface using a wire wound rod type, No. 7 bar coater manufactured by RD Specialties. After coating, the adhesive sheet B was heated and dried in an oven at 110° C. for 2 minutes to volatilize and remove the solvent, thereby obtaining an adhesive sheet B including an adhesive layer in which the UV absorber and HDDA were dissolved.

[0369] (Example 23)

[0370] An adhesive sheet B including an adhesive layer in which the ultraviolet absorber and HDDA were dissolved was obtained by coating an ethyl acetate solution obtained by diluting an ultraviolet absorber (Tinuvin 928, manufactured by BASF) to a concentration of 12 wt%, diluting hexanediol diacrylate (HDDA) to a concentration of 30 wt%, and diluting a photopolymerization initiator (Omnirad 819, manufactured by IGM Resins B.V.) to a concentration of 0.5 wt%. The same procedures as in Example 22 were performed to obtain an adhesive sheet B including an adhesive layer in which the ultraviolet absorber and HDDA were dissolved.

[0371] (Example 24)

[0372] An adhesive sheet B including an adhesive layer in which HDDA was dissolved was obtained in the same manner as in Example 22 except that hexanediol diacrylate (HDDA) was diluted to a concentration of 20 wt % and an ethyl acetate solution of a photopolymerization initiator (Omnirad 819, manufactured by IGM Resins BV) was diluted to a concentration of 0.3 wt %.

[0373] (Example 25)

[0374] An adhesive sheet B including an adhesive layer in which HDDA was dissolved was obtained in the same manner as in Example 22 except that hexanediol diacrylate (HDDA) was diluted to a concentration of 30 wt % and an ethyl acetate solution of a photopolymerization initiator (Omnirad 819, manufactured by IGM Resins BV) was diluted to a concentration of 0.5 wt %.

[0375] <Evaluation>

[0376] The adhesive sheets obtained in Examples 22 to 25 were left to stand for 7 days in the same manner as in Examples 12 to 17, and then evaluated for the above-mentioned "transmittance evaluation", "adhesion evaluation" and "elastic modulus evaluation". The transmittance evaluation and adhesion evaluation were performed on the adhesive sheets before curing by ultraviolet irradiation. The results are shown in Table 5.

[0377] [Table 5]

[0378]

[0379] It can be seen that compared with the adhesive sheets of Examples 24 and 25 obtained by applying a solution without an ultraviolet absorber, the adhesive sheets of Examples 22 and 23 obtained by applying a solution containing an ultraviolet absorber in addition to a photopolymerization initiator and a crosslinking agent have increased storage modulus after curing, and improved bonding reliability. This is believed to be because the ultraviolet absorber that absorbs ultraviolet rays generates heat and promotes the curing reaction.

[0380] Modifications of the present invention are described below.

[0381] [Supplementary Note 1] A method for producing an adhesive sheet, characterized in that it comprises the following steps:

[0382] forming an adhesive layer formed of a transparent adhesive matrix material on a support,

[0383] The adhesive layer is cured.

[0384] Prepare the solution of additives,

[0385] The solution is applied to one surface of the cured adhesive layer, so that the additive contained in the solution permeates from the one surface of the adhesive layer in the thickness direction.

[0386] The adhesive layer is dried.

[0387] [Supplementary Note 2] The method for producing an adhesive sheet according to Supplementary Note 1, wherein the solution of the additive is a solution obtained by dissolving the additive in a solvent,

[0388] The manufacturing method comprises the following steps:

[0389] By drying the adhesive layer, the solvent of the solution is evaporated.

[0390] [Supplement 3] The method for producing an adhesive sheet according to Supplement 1 or 2, further comprising the following step:

[0391] A release sheet is attached to the surface of the pressure-sensitive adhesive layer on the opposite side to the support.

[0392] [Supplement 4] The method for producing a pressure-sensitive adhesive sheet according to any one of Supplements 1 to 3, wherein the additive is at least one selected from the group consisting of a polymerization initiator, a crosslinking agent, a UV absorber, a rust preventive, and an antistatic agent.

[0393] [Supplementary Note 5] The method for producing a pressure-sensitive adhesive sheet according to Supplementary Note 4, wherein the additive is at least one selected from the group consisting of a polymerization initiator and a cross-linking agent.

[0394] [Supplementary Note 6] The method for producing a pressure-sensitive adhesive sheet according to Supplementary Note 5, wherein the additive further includes a UV absorber.

[0395] [Supplement 7] The method for producing an adhesive sheet according to any one of Supplements 1 to 6, wherein the adhesive matrix material comprises a first polymerization initiator and a first crosslinking agent,

[0396] The curing is based on the reaction of the first polymerization initiator and the first crosslinking agent.

[0397] The aforementioned additive is at least one selected from the group consisting of a second polymerization initiator and a second cross-linking agent.

[0398] [Supplementary Note 8] The method for producing a pressure-sensitive adhesive sheet according to Supplementary Note 7, wherein the first polymerization initiator and the second polymerization initiator are the same.

[0399] [Supplementary Note 9] A method for producing an optical member stacked body, the method comprising producing an optical member stacked body including a substrate formed of an optical member and a pressure-sensitive adhesive layer, the method comprising the following steps:

[0400] The adhesive layer of the adhesive sheet obtained by the method described in Supplementary Note 7 or 8 is bonded to the main surface of the substrate formed of the optical member.

[0401] The adhesive layer is cured by reaction of at least one selected from the group consisting of the second polymerization initiator and the second cross-linking agent.

[0402] [Supplementary Note 10] The method for producing an optical member laminate according to Supplementary Note 9, wherein the main surface of the substrate formed of the optical member has a printed layer,

[0403] The adhesive layer is bonded to the printed layer so as to fill in a height difference between the main surface of the substrate formed of the optical member and the printed layer.

[0404] [Supplementary Note 11] An adhesive sheet comprising a support and a transparent adhesive layer on the support,

[0405] The adhesive layer is formed of a transparent adhesive matrix material and is a single layer having two opposing main surfaces.

[0406] The adhesive layer contains an additive dissolved therein.

[0407] When the above-mentioned single-layer adhesive layer is divided into two equal parts along the thickness direction,

[0408] The concentration of the additive in a region to which one of the two main surfaces, ie, the first main surface, belongs is different from the concentration of the additive in a region to which the other main surface, ie, the second main surface, belongs.

[0409] [Appendix 12] The adhesive sheet according to Appendix 11, wherein the adhesive layer is a cured adhesive layer.

[0410] [Supplement 13] The adhesive sheet according to Supplement 11 or 12, wherein the second main surface faces the support, and the concentration of the additive in the region to which the first main surface belongs is higher than the concentration of the additive in the region to which the second main surface belongs.

[0411] [Appendix 14] The adhesive sheet according to any one of Appendices 11 to 13, wherein the single adhesive layer has a concentration gradient of the additive along a thickness direction.

[0412] [Supplementary Note 15] The adhesive sheet according to any one of Supplementary Notes 11 to 14, wherein the support is formed of a release sheet.

[0413] [Supplementary Note 16] The adhesive sheet according to Supplementary Note 15, wherein the support body formed of a release sheet is disposed on both surfaces of the adhesive layer.

[0414] [Supplement 17] The adhesive sheet according to any one of Supplements 11 to 16, wherein the additive is at least one selected from the group consisting of a polymerization initiator, a crosslinking agent, a UV absorber, a rust preventive, and an antistatic agent.

[0415] [Supplementary Note 18] The adhesive sheet according to Supplementary Note 17, wherein the additive is at least one selected from the group consisting of a polymerization initiator and a cross-linking agent.

[0416] [Supplementary Note 19] The adhesive sheet according to Supplementary Note 18, wherein the additive further includes an ultraviolet absorber.

[0417] [Supplement 20] The adhesive sheet according to any one of Supplements 12 to 19, wherein the adhesive matrix material comprises a first polymerization initiator and a first crosslinking agent,

[0418] The curing is based on the reaction of the first polymerization initiator and the first crosslinking agent.

[0419] The aforementioned additive is at least one selected from the group consisting of a second polymerization initiator and a second cross-linking agent.

[0420] [Appendix 21] The adhesive sheet according to Appendix 20, wherein the first polymerization initiator and the second polymerization initiator are the same.

[0421] [Appendix 22] The adhesive sheet according to any one of Appendices 11 to 21, wherein the adhesive layer has a thickness of 5 to 500 μm.

[0422] [Supplementary Note 23] An optical member stack comprising:

[0423] a substrate formed of optical components; and

[0424] Adhesive layer,

[0425] The adhesive layer is laminated on the main surface of the substrate formed of the optical member.

[0426] The adhesive layer is a cured product of the adhesive layer of the adhesive sheet according to any one of Supplementary Notes 18 to 21.

[0427] [Appendix 24] The optical member laminate according to Appendix 23, wherein the main surface of the substrate formed of the optical member has a printed layer,

[0428] The pressure-sensitive adhesive layer is laminated so as to fill a height difference between the main surface of the substrate formed of the optical member and the printed layer.

[0429] [Appendix 25] The optical member laminate according to Appendix 23 or 24, wherein the cured product is a cured product resulting from a reaction of at least one selected from the group consisting of the second polymerization initiator and the second cross-linking agent.

[0430] Industrial Applicability

[0431] The present invention is useful for a method for producing a pressure-sensitive adhesive sheet having a transparent pressure-sensitive adhesive layer that can be used to bond a transparent optical member to another optical member, and a pressure-sensitive adhesive sheet obtainable by the production method.

[0432] Description of Reference Numerals

[0433] 10 Adhesive layer (before curing)

[0434] 10a Adhesive layer (after curing)

[0435] S, S1, S2, S3 Support (peel sheet)

[0436] U: Ultraviolet

[0437] 11 Additives

[0438] 11a Second polymerization initiator

[0439] 11b Second cross-linking agent

[0440] 11c Cross-linked structure

[0441] 12 Additive solution

[0442] 13 Solvents

[0443] 31, 32 Optical components

[0444] 21 Adhesive layer (after curing)

[0445] 21a Main surface (first surface) of adhesive layer

[0446] 21b Main surface (second surface) of adhesive layer

[0447] 41 Adhesive layer (before curing)

[0448] 41a Main surface (first surface) of adhesive layer

[0449] 41b Main surface (second surface) of adhesive layer

[0450] 42 Optical components

[0451] 42a Main surface of optical component

[0452] 43 Printing layer

Claims

1. A method for producing an adhesive sheet, characterized in that: Including the following processes: forming an adhesive layer formed of a transparent adhesive matrix material on a support, curing the adhesive layer, Prepare the solution of additives, The solution of the additive is a solution obtained by dissolving the additive in a solvent. The solution is applied to one surface of the cured adhesive layer, so that the additive contained in the solution permeates from the one surface of the adhesive layer in the thickness direction. The adhesive layer is allowed to dry.

2. The method for producing an adhesive sheet according to claim 1, wherein: The manufacturing method comprises the following steps: The solvent of the solution is evaporated by drying the adhesive layer.

3. The method for producing an adhesive sheet according to claim 1 or 2, further comprising the following steps: A release sheet is attached to the surface of the pressure-sensitive adhesive layer on the opposite side to the support.

4. The method for producing an adhesive sheet according to claim 1 or 2, wherein: The additive is at least one selected from the group consisting of a polymerization initiator, a cross-linking agent, an ultraviolet absorber, a rust preventive, and an antistatic agent.

5. The method for producing an adhesive sheet according to claim 4, wherein: The additive is at least one selected from the group consisting of a polymerization initiator and a cross-linking agent.

6. The method for producing an adhesive sheet according to claim 5, wherein: The additives further include an ultraviolet absorber.

7. The method for producing an adhesive sheet according to claim 1 or 2, wherein: The adhesive matrix material comprises a first polymerization initiator and a first cross-linking agent, The curing is based on the reaction of the first polymerization initiator and the first cross-linking agent, The additive is at least one selected from the group consisting of a second polymerization initiator and a second cross-linking agent.

8. The method for producing an adhesive sheet according to claim 7, wherein: The first polymerization initiator is the same as the second polymerization initiator.

9. A method for producing an optical member stacked body, the method comprising producing an optical member stacked body including a substrate formed of an optical member and a pressure-sensitive adhesive layer, the method comprising the following steps: The adhesive layer of the adhesive sheet obtained by the method according to claim 7 or 8 is bonded to the main surface of the substrate formed of the optical member, The adhesive layer is cured by a reaction of at least one selected from the group consisting of the second polymerization initiator and a second cross-linking agent.

10. The method for producing an optical member stack according to claim 9, wherein: The main surface of the substrate formed of the optical member has a printed layer, The adhesive layer is bonded to the printed layer so as to fill a height difference between the main surface of the substrate formed of the optical member and the printed layer.

11. An adhesive sheet obtained by the method for producing an adhesive sheet according to any one of claims 1 to 8, characterized in that: The invention comprises a support and a transparent adhesive layer on the support, The adhesive layer is formed of a transparent adhesive matrix material and is a single layer having two opposite main surfaces. The adhesive layer contains an additive dissolved therein. When the single adhesive layer is divided into two equal parts along the thickness direction, The concentration of the additive in a region to which one of the two main surfaces, ie, the first main surface, belongs is different from the concentration of the additive in a region to which the other main surface, ie, the second main surface, belongs.

12. The adhesive sheet according to claim 11, wherein The adhesive layer is a cured adhesive layer.

13. The adhesive sheet according to claim 11 or 12, characterized in that: The second main surface faces the support body, and the concentration of the additive in the region to which the first main surface belongs is higher than the concentration of the additive in the region to which the second main surface belongs.

14. The adhesive sheet according to claim 11 or 12, characterized in that: The single-layer adhesive layer has a concentration gradient of the additive along the thickness direction.

15. The adhesive sheet according to claim 11 or 12, characterized in that: The support is formed of a release sheet.

16. The adhesive sheet according to claim 15, characterized in that The support body formed of a release sheet is arranged on both surfaces of the pressure-sensitive adhesive layer.

17. The adhesive sheet according to claim 11 or 12, wherein The additive is at least one selected from the group consisting of a polymerization initiator, a cross-linking agent, an ultraviolet absorber, a rust preventive, and an antistatic agent.

18. The adhesive sheet according to claim 17, wherein The additive is at least one selected from the group consisting of a polymerization initiator and a cross-linking agent.

19. The adhesive sheet according to claim 18, wherein The additives further include an ultraviolet absorber.

20. The adhesive sheet according to claim 12, wherein The adhesive matrix material comprises a first polymerization initiator and a first cross-linking agent, The curing is curing based on the reaction of the first polymerization initiator and the first cross-linking agent, The additive is at least one selected from the group consisting of a second polymerization initiator and a second cross-linking agent.

21. The adhesive sheet according to claim 20, wherein The first polymerization initiator is the same as the second polymerization initiator.

22. The adhesive sheet according to claim 11 or 12, wherein The thickness of the adhesive layer is 5-500 μm.

23. An optical component stack, comprising: a substrate formed of optical members; and Adhesive layer, The adhesive layer is laminated on the main surface of the substrate formed of the optical member, The adhesive layer is a cured product of the adhesive layer of the adhesive sheet according to any one of claims 18 to 21.

24. The optical member stack according to claim 23, wherein The main surface of the substrate formed of the optical member has a printed layer, The adhesive layer is laminated so as to fill a height difference between the main surface of the substrate formed of the optical member and the printed layer.

25. The optical member stack according to claim 23 or 24, wherein The cured product is a cured product obtained by a reaction of at least one selected from the group consisting of the second polymerization initiator and a second cross-linking agent.

Citation Information

Patent Citations

  • Transparent double-sided adhesive sheet for image display device, and image display device

    JP2012211305A

  • Adhesive composition and adhesive film

    JP2016128537A

  • Adhesive composition, adhesive agent, and adhesive sheet

    WO2015145767A1

  • Ultraviolet ray-curable adhesive sheet, and adhesive sheet

    WO2016170875A1

  • Adhesive agent sheet having transparent adhesive agent layer

    CN105189678A